Electrolyte materials and formation methods

By optimizing the chemical composition and crystallization structure of the halide material, the problems of the synthesis and cost of existing solid electrolyte materials at high temperatures are solved, and the formation of solid electrolyte materials with improved performance is achieved at room temperature, which improves the safety and stability of the material.

CN116097487BActive Publication Date: 2025-04-15SAINT GOBAIN CERAMICS & PLASTICS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280005925.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-05-17
Publication Date
2025-04-15
Estimated Expiration
2042-05-17

AI Technical Summary

Technical Problem

Existing solid electrolyte materials are synthesized at high temperatures and are costly, and they may release toxic gases when water and heat react, which poses safety risks.

Method used

Using a halide material including at least two halide anions, a solid electrolyte material with improved ionic conductivity, electrochemical stability and mechanical properties is formed through the optimization of specific chemical composition and crystallization structure.

Benefits of technology

The formation of deformable solid electrolyte materials at room temperature is achieved, reducing the cost of large-scale production and improving the safety and performance stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116097487B_ABST
    Figure CN116097487B_ABST
Patent Text Reader

Abstract

A solid electrolyte material may include Li 3‑x‑f M f RE 1‑ y Me k y (Cl 1‑u‑p‑q Br u F p I q ) 6‑x+y*(k‑3) The halide material of the present invention comprises at least two halide anions. The halide material may comprise one or more impurity phases with reduced content, including a binary halide phase, an oxyhalide phase, or a ternary halide phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The following relates to a solid electrolyte material and a method of forming the same, and in particular, to a solid electrolyte material including a halide material containing at least two halide anions and a method of forming the same. Background Art

[0002] Solid-state lithium batteries are expected to provide higher energy density and faster recharge times and cause fewer safety issues compared to conventional lithium-ion batteries by implementing lithium metal anodes. Current solid electrolyte materials include oxides, halides, sulfides, fluorides, and solid polymer electrolytes.

[0003] Oxide-based materials have been considered safe and have good chemical and electrochemical stability. The synthesis of these compounds usually uses high temperatures above 1000°C-1200°C. Oxide-based materials are generally dense, rigid and brittle, with ionic conductivity (IC) as high as 1.0 mS / cm at room temperature. RT ).

[0004] Halide compounds, such as chlorides and bromides, are generally safe and have good chemical and electrochemical stability, room temperature deformability and plasticity, allowing relatively high compatibility with active electrode materials. Halides are generally hygroscopic and form hydrates or undergo hydrolysis when exposed to moisture. Halide solid electrolytes, such as Li3YCl6 (LYC) and Li3YBr6 (LYB), are synthesized using a solid-state synthesis method based on high-energy ball milling. The synthesis is challenging for large-scale production applications, further because of the use of expensive binary halide reactants and / or high temperature annealing.

[0005] Fluorides are very similar to oxides in their physical, chemical, and electrochemical properties, but typically have IC values ​​below 1 mS / cm. RT value.

[0006] Sulfides have relatively high ionic conductivity. For example, IC RT can be as high as 25mS / cm, while commercially relevant sulfide or thiophosphate solid electrolytes can reach 2mS / cm-10mS / cm. Sulfide materials are mechanically softer and deformable. However, sulfide materials tend to have poor electrochemical stability and raise safety issues due to the risk of releasing toxic H2S gas when accidentally reacting with water and heat. In addition, high surface area sulfide solid electrolyte powders pose a particularly high H2S risk due to their increased reactivity even in ambient humidity.

[0007] Solid polymer electrolytes containing lithium salts generally have relatively low IC RT value and electrochemical stability.

[0008] Industry continues to need improved solid electrolyte materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The present disclosure may be better understood, and its numerous features and advantages made apparent to those skilled in the art by referencing the accompanying drawings.

[0010] Figure 1A and Figure 1B Included is a graphic representation of the readings of an XRD pattern containing halide materials.

[0011] Figure 2 Included are graphical representations of readings of XRD patterns containing additional halide materials.

[0012] Figure 3 Included is a flow chart illustrating a process of forming a solid electrolyte material according to one embodiment.

[0013] Figure 4 Included is an illustration of a portion of a cross-section of an exemplary electrochemical device.

[0014] Figure 5 and Figure 6 Included are cyclic voltammetry VA plots of battery samples.

[0015] Fig. 7A and Figure 7B Included are illustrations of exemplary electrochemical devices according to embodiments herein.

[0016] Figure 8 Included is a graph of Cl concentration versus ionic conductivity of a halide material according to one embodiment.

[0017] Fig. 9A and Fig. 9B Included are graphical representations of readings of XRD patterns containing additional halide materials.

[0018] Fig.10 Included is a diagram of a formation process according to one embodiment. Fig.11A and Fig. 11B Included is a graphical representation of the electrochemical stability of halide materials.

[0019] The skilled person will appreciate that the elements in the drawings are shown for simplicity and clarity and are not necessarily drawn to scale. For example, the size of some of the elements in the drawings may be enlarged relative to other elements to help improve understanding of the embodiments of the present invention. The same reference numerals are used in different drawings to indicate similar or identical items. DETAILED DESCRIPTION

[0020] The following description in conjunction with the accompanying drawings is provided to help understand the teachings disclosed herein. The following discussion will focus on specific implementations and embodiments of the teachings. This focus is provided to help describe the teachings and should not be interpreted as a limitation on the scope or applicability of the teachings.

[0021] As used herein, the terms "comprises, comprising," "includes, including," "has, having," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that includes a list of features is not necessarily limited to only those features, but may include other features not expressly listed or inherent to such process, method, article, or apparatus. In addition, unless expressly stated to the contrary, "or" refers to inclusion, not exclusivity. For example, a condition A or B is satisfied by any of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exists).

[0022] The use of "a" or "an" to describe elements and components described herein is for convenience only and to give a general sense of the scope of the invention. The description should be understood to include one or at least one and the singular also includes the plural, or vice versa, unless it is clearly indicated otherwise.

[0023] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.The materials, methods, and examples are illustrative only and not intended to be limiting.

[0024] Embodiments herein relate to solid electrolyte materials, including halide materials. In one embodiment, the halide material may include at least two halide anions, at least one alkali metal element, and at least one other metal element. In one embodiment, the solid electrolyte material may include a quaternary halide material. In another embodiment, the solid electrolyte material may include a halide material having one or more improved properties compared to conventional metal halide materials. For example, the halide material may have improved purity, crystalline structure characteristics, or both. In another example, the halide material may have improved ionic conductivity, electronic conductivity, mechanical properties, electrochemical thermodynamic stability, or any combination thereof. In an embodiment, the solid electrolyte material may be used to form an electrolyte, a coating, a cathode electrolyte and / or an anode electrolyte, or another component of an electrochemical device. In an exemplary application, the solid electrolyte material may be particularly suitable for forming a cathode electrolyte or an anode electrolyte due to its improved properties (such as improved interface contact and wettability). In a specific embodiment, the solid electrolyte material may be a suitable component of a solid-state lithium battery pack.

[0025] Additional embodiments relate to methods of forming solid electrolyte materials (including halide materials). The methods can allow for improved formation of solid electrolyte materials and promote the formation of solid electrolyte materials with improved properties. The methods can be suitable for large-scale production of ion-conducting materials in a cost-effective manner.

[0026] In one embodiment, the solid electrolyte material may include Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p- q Br u F p I q ) 6-x+y*(k-3) The halide material represented by is a halide material, wherein the halide material includes at least two halide anions, -1<=x<=1, 0<=y<=1, 0<=u<1, 0<=p<=1 / 3, 0<=q<=1 / 6, 0<(u+p+q)<1 and 0<=f<=0.3.

[0027] The halide anion may be an element selected from the group consisting of F, Cl, Br and I. M may include at least one alkali metal other than Li. In a specific example, M may be one or more alkali metal elements selected from the group consisting of Na, K, Cs, Rb and Fr. In another example, M may include Na, K, Cs or a combination thereof. In a more specific case, M may include at least one of Na and K. In an even more specific example, M may consist of Na or K or a combination thereof.

[0028] RE may include at least one rare earth element selected from the group including Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu. For example, RE may include any combination of Sc, Y, La, Gd. In another example, RE may include Y, Ce, Gd, Er, La, Yb or a combination thereof. In a specific example, RE may be composed of one or more elements selected from the group consisting of: Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu. In a more specific example, RE may be composed of Ce, Gd, Er, La, Yb or a combination thereof. In another more specific example, RE may be composed of Y, Gd or a combination thereof. In even more specific cases, RE may be composed of Y or Gd.

[0029] Me may include at least one metallic element different from RE. For example, Me may be one or more elements selected from the group consisting of: IIIB group elements, IVB group elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, Sn, Pb, Bi, Sb, Mg, Ca, Ga or Ge. In another example, Me may include Y, Ce, Gd, Er, Sm, Eu, Pr, Tb, Al, Zr, La, Yb, Mg, Zn, Sn, Mg and Ca, or any combination thereof. In a specific example, Me may be at least one element selected from the group consisting of Gd, Yb, Zr, Zn, Mg, Al and Ca. In a more specific example, Me may be Gd, Zr, Hf, Zn or any combination thereof. As used herein, the element family conforms to Handbook of the Elements, 8th edition, 1998.

[0030] Me may have a valence k. In the case where Me includes more than one metal element, k may be the average of the total valence of each Me metal element. For example, when Me includes equimolar amounts of trivalent elements and tetravalent elements, k=(3+4) / 2=3.5. For another example, when Me includes equimolar amounts of divalent elements and tetravalent elements, k=(2+4) / 2=3. In certain aspects, k may be 2 or 3 or 4 or 5.

[0031] In one embodiment, the halide material may have an improved purity. For example, compared with the corresponding conventional halide material, the halide material may have one or more impurity phases with a reduced content. As used herein, the conventional corresponding halide material is intended to refer to a halide material having the same formula as the halide material of the embodiment of the present invention, but formed by a method different from the method described in the embodiment of the present invention. On the one hand, the impurity phase may include one or more phases of unreacted starting materials, by-products, products or intermediates produced by degradation of the halide material, etc., or any combination thereof. In another aspect, the impurity phase may include one or more phases of binary halides, ternary halides, oxyhalides, oxynitrides, or any combination thereof.

[0032] In one embodiment, the halide material may include a binary halide phase with a reduced total content compared to conventional corresponding halide materials. The binary halide may include cations of metal elements selected from the group consisting of Li, M, Me and RE. On the one hand, the halide material may include a total content of no more than 10 wt % of the binary halide phase relative to the total weight of the halide material, such as no more than 9 wt % of the total content of the binary halide phase relative to the total weight of the halide material, no more than 8 wt %, no more than 7 wt %, no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of the binary halide phase. In another aspect, the halide material may include a total content of binary halide phases of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, or at least 0.05 wt % relative to the total weight of the halide material. In further aspects, the halide material may include a total content of binary halide phases within a range including any of the minimum percentages and maximum percentages described herein. In specific aspects, the halide material may be substantially free of binary halide phases.

[0033] The content of one or more impurity phases that may be present in the halide material can be determined by using known techniques, such as powder X-ray diffraction analysis of the halide material or innovative laser Raman mapping. X-ray diffraction analysis may be particularly suitable when the content of the impurity phase is at least 1% by weight relative to the total weight of the halide material.

[0034] In one embodiment, the binary phase may include one or more alkali halide phases. In one aspect, the halide material may include an alkali halide phase in a total content of no more than 7 wt % relative to the total weight of the halide material, including no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of the alkali halide phase relative to the total weight of the halide material. In each case, the halide material may include a total content of at least 0.0001 wt % of the alkali halide phase relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt % or at least 0.05 wt % of the alkali halide phase relative to the total weight of the halide material. In other cases, the halide material may include a total content of the alkali halide phase within a range including any of the minimum percentages and maximum percentages described herein. In certain examples, the halide material can be substantially free of alkali halide phases.

[0035] In a particular embodiment, the halide material may include a total content of no more than 7 wt % of the lithium halide phase relative to the total weight of the halide material. The lithium halide phase may include one or more phases of LiCl phase, LiBr phase, LiI phase and LiF phase. On the one hand, the halide material may include a total content of no more than 6 wt % of the lithium halide phase relative to the total weight of the halide material, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of the lithium halide phase. In each case, the halide material may include a total content of at least 0.0001 wt % of the lithium halide phase relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt % or at least 0.05 wt % of the total content of the lithium halide phase relative to the total weight of the halide material. In further aspects, the halide material can include a total content of lithium halide phase within a range including any of the minimum and maximum percentages described herein. In particular aspects, the halide material can be substantially free of lithium halide phase.

[0036] In one embodiment, the binary phase may include one or more rare earth halide phases, such as YX3 phase, wherein X represents a halide anion. In one aspect, the halide material may include a total content of rare earth halide phases of not more than 10 wt % relative to the total weight of the halide material, such as not more than 9 wt %, not more than 8 wt %, not more than 7 wt %, not more than 6 wt %, not more than 5 wt %, not more than 4 wt %, not more than 3 wt %, not more than 2 wt %, not more than 1 wt %, or not more than 0.5 wt % of the total content of rare earth halide phases. In another aspect, the halide material may include a total content of at least 0.0001 wt % of rare earth halide phases relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt % or at least 0.05 wt % of the total content of rare earth halide phases relative to the total weight of the halide material. In further aspects, the halide material can include a total content of rare earth halide phases within a range including any of the minimum and maximum percentages described herein. In particular aspects, the halide material can be substantially free of rare earth halide phases.

[0037] In certain embodiments, the binary halide phase may include one or more YX3 phases, such as one or more phases of YCl3, YBr3, YI3, or YF3. In one aspect, the halide material may include a total content of YX3 phases of no more than 10 wt %, such as no more than 9 wt %, no more than 8 wt %, no more than 7 wt %, no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of YX3 phases. In another aspect, the halide material may include a total content of at least 0.0001 wt % of the YX3 phase relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, or at least 0.05 wt % of the total content of the YX3 phase relative to the total weight of the halide material. In further aspects, the halide material can include a total content of the YX3 phase within a range including any of the minimum and maximum percentages described herein. In particular aspects, the halide material can be substantially free of the YX3 phase.

[0038] In one embodiment, compared with conventional corresponding halide materials, halide materials may include one or more oxyhalide phases of reduced content. Oxyhalides may include cations of metal elements selected from the group consisting of M, Me and RE. On the one hand, halide materials may include a total content of oxyhalide phases not greater than 7 wt % relative to the total weight of halide materials, such as oxyhalide phases not greater than 6 wt %, not greater than 5 wt %, not greater than 4 wt %, not greater than 3 wt %, not greater than 2 wt %, not greater than 1 wt %, or not greater than 0.5 wt % oxyhalide phases relative to the total weight of halide materials. On the other hand, halide materials may include a total content of at least 0.0001 wt % of oxyhalide phases relative to the total weight of halide materials, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt % or at least 0.05 wt % of oxyhalide phases relative to the total weight of halide materials. In further aspects, the halide material can include a total content of oxyhalide phase within a range including any of the minimum and maximum percentages described herein. In particular aspects, the halide material can be substantially free of oxyhalide phase.

[0039] The total content of the water-insoluble impurity phase can be determined by using the water method described below. 50 g of the halide material can be dissolved in distilled H2O. The solution can be filtered through a 0.2 micron microporous filter. The insoluble material can be collected and weighed. The collected insoluble material may include water-insoluble impurities in a hydrated form present in the halide material. For example, at least most of the water-insoluble impurities present in the halide material may be oxyhalides of rare earth elements, rare earth oxides, oxyhalides of Me, MeO, or any combination thereof. The weight of the collected insoluble material can be used to determine the total content of water-insoluble impurities in the halide material. Using the insoluble impurity phase of the metal oxyhalide MeOX as an example, the precipitated hydrated impurity form can be represented by MeX(OH)2, and the content of MeOX can be measured using the formula C MeOX =C MeOHX ×(MW MeOX / MW MeOHX ) is determined, where C MeOX represents the weight content of MeOX relative to the weight of the halide material, C MOHX The weight content of precipitated MeX(OH)2 relative to the weight of halide material, MW MeOX represents the molar mass of MeOX, and MW MeOHXRepresents the molar mass of MeX(OH)2. In the case where the synthesis of the halide material may include melting and solidification, trace amounts of organic residues may be present on the surface of the synthesis block of the halide material. Organic residues are carbon concentrated on the surface of the block and can be removed by using a scraper. Trace amounts of carbon may originate from the pyrolysis of organic impurities that may be present in one or more raw materials for synthesizing the halide material.

[0040] In one embodiment, the halide material may include a reduced content of water-insoluble impurity phases. In one aspect, the halide material may include a total content of water-insoluble impurity phases less than 0.11 wt % relative to the total weight of the halide material, such as no greater than 0.1 wt %, no greater than 0.09 wt %, no greater than 0.08 wt %, no greater than 0.07 wt %, no greater than 0.05 wt %, no greater than 0.04 wt %, no greater than 0.03 wt %, no greater than 0.01 wt %, no greater than 0.008 wt %, no greater than 0.006 wt %, no greater than 0.004 wt %, or no greater than 0.003 wt %, relative to the total weight of the halide material. In another aspect, the halide material may include a total content of at least 0.0001 wt % of water-insoluble impurity phases relative to the total weight of the halide material, such as at least 0.0003 wt %, at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, at least 0.013 wt %, at least 0.015 wt %, at least 0.02 wt %, at least 0.03 wt % or at least 0.05 wt % of water-insoluble impurity phases relative to the total weight of the halide material. In a further aspect, the halide material may include a total content of water-insoluble impurity phases within a range including any of the minimum percentages and maximum percentages described herein. In a particular aspect, the halide material may be substantially free of water-insoluble impurity phases. In each case, a majority of the water-insoluble impurity phases may include one or more phases of rare earth oxyhalides, oxyhalides of Me, rare earth oxides, oxides of Me, or any combination thereof. In another instance, the water-insoluble impurity phase can consist essentially of one or more phases of rare earth oxyhalides, Me oxyhalides, rare earth oxides, Me oxides, or any combination thereof.

[0041] In one embodiment, the oxyhalide phase may include one or more rare earth oxyhalide phases. In one aspect, the halide material may include a total content of no more than 7 wt%, no more than 6 wt%, no more than 5 wt%, no more than 4 wt%, no more than 3 wt%, no more than 2 wt%, no more than 1 wt%, or no more than 0.5 wt% of the rare earth oxyhalide phase. In a particular aspect, the total content of the rare earth oxyhalide phase may be or less than 0.3 wt%, such as less than 0.2 wt%, less than 0.12 wt%, less than 0.11 wt%, less than 0.10 wt%, no more than 0.09 wt%, no more than 0.07 wt%, no more than 0.05 wt%, or no more than 0.03 wt% of the rare earth oxyhalide phase relative to the total weight of the halide material. In another aspect, the halide material may include a total content of rare earth oxyhalide phases of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, at least 0.02 wt %, or at least 0.05 wt % relative to the total weight of the halide material. In further aspects, the halide material may include a total content of rare earth oxyhalide phases within a range including any of the minimum and maximum percentages described herein. In particular aspects, the halide material may be substantially free of rare earth oxyhalide phases, which may be represented by REOX, wherein X is a halogen and RE is a rare earth element.

[0042] In one embodiment, the halide material may include one or more ternary halide phases with a reduced total content compared to conventional corresponding halide materials. Exemplary ternary halides may include two metal cations and one halide anion, such as alkali metal-rare earth metal halides, or one metal element and two halide anions, or both. Exemplary metal cations may include cations of Li, M, RE and / or Me metal elements. On the one hand, the halide material may include a total content of no more than 7 wt % of the ternary halide phase relative to the total weight of the halide material, such as no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of the ternary halide phase. In another aspect, the halide material may include a total content of ternary halide phases of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, or at least 0.05 wt % relative to the total weight of the halide material. In further aspects, the halide material may include a total content of ternary halide phases within a range including any of the minimum percentages and maximum percentages described herein. In particular aspects, the halide material may be substantially free of ternary halide phases.

[0043] In one embodiment, the ternary phase may include one or more lithium-rare earth halide phases, such as lithium yttrium halide phases. In one aspect, the halide material may include a total content of lithium-rare earth halide phases of not more than 7 wt %, not more than 5 wt %, not more than 3 wt %, not more than 2 wt %, not more than 1 wt %, or not more than 0.5 wt % of the total content of lithium-rare earth halide phases relative to the total weight of the halide material. In another aspect, the halide material may include a total content of lithium-rare earth halide phases of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt % or at least 0.05 wt % of the total content of lithium-rare earth halide phases relative to the total weight of the halide material. In another aspect, the halide material may include a total content of lithium-rare earth halide phases within a range including any of the minimum percentages and maximum percentages described herein. In certain aspects, the halide material can be substantially free of lithium-rare earth halide phases.

[0044] In certain embodiments, the ternary halide phase may include no more than 7 wt % of one or more ternary halide phases including two anions, such as YBr, relative to the total weight of the halide material. x Cl y or LiBrx Cl y ), such as no more than 6 wt%, no more than 5 wt%, no more than 4 wt%, no more than 3 wt%, no more than 2 wt%, no more than 1 wt%, or no more than 0.5 wt% of the total content of the ternary halide phase including two anions. In each case, the halide material may include at least 0.0001 wt% of the total content of the ternary halide phase including two halide anions relative to the total weight of the halide material, such as at least 0.0005 wt%, at least 0.001 wt%, at least 0.005 wt%, at least 0.01 wt%, or at least 0.05 wt% of the total content of the ternary halide phase including two anions relative to the total weight of the halide material. In other aspects, the halide material may include a total content of the ternary halide phase including two anions within a range including any of the minimum percentages and maximum percentages described herein. In specific aspects, the halide material may be substantially free of the ternary halide phase including two anions.

[0045] In one embodiment, the halide material may include one or more nitride-based phases with a reduced content compared to conventional corresponding halide materials. The nitride-based phase may include one or more phases of a nitride oxide phase, a carbon nitride phase, or a nitride phase. The nitride phase may include cations of a metal element selected from the group consisting of Li, M, RE, and Me. In one aspect, the halide material may include a total content of the nitride-based phase of no more than 7 wt % relative to the total weight of the halide material, such as no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of the nitride-based phase. In another aspect, the halide material may include a total content of nitride-based phase of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, or at least 0.05 wt % relative to the total weight of the halide material. In further aspects, the halide material may include a total content of nitride-based phase within a range including any of the minimum and maximum percentages described herein. In a particular aspect, the halide material may be substantially free of nitride-based phase.

[0046] In one embodiment, the halide material may include a reduced content of one or more oxynitride phases, such as REO, as compared to conventional corresponding halide materials. x N yPhase. The oxynitride may include cations of a metal element selected from the group consisting of Me and RE. In one aspect, the halide material may include a total content of the oxynitride phase of no more than 7 wt % relative to the total weight of the halide material, such as no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of the oxynitride phase. In another aspect, the halide material may include a total content of at least 0.0001 wt % of the oxynitride phase relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt % or at least 0.05 wt % of the total content of the oxynitride phase relative to the total weight of the halide material. In another aspect, the halide material may include a total content of the oxynitride phase within a range including any of the minimum percentages and maximum percentages described herein. In a particular aspect, the halide material may be substantially free of the oxynitride phase.

[0047] In one embodiment, the halide material may include a reduced content of one or more carbon nitride phases, such as REC, compared to conventional corresponding halide materials. x N y phase. The carbon nitride may include cations of a metal element selected from the group consisting of Me and RE. In one aspect, the halide material may include a total content of the carbon nitride phase of no more than 7 wt % relative to the total weight of the halide material, such as no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of the carbon nitride phase relative to the total weight of the halide material. In another aspect, the halide material may include a total content of the carbon nitride phase of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, or at least 0.05 wt % of the total content of the carbon nitride phase relative to the total weight of the halide material. In a further aspect, the halide material may include a total content of the carbon nitride phase within a range including any of the minimum percentages and maximum percentages described herein. In certain aspects, the halide material can be substantially free of a carbon nitride phase.

[0048] In one embodiment, the halide material may include a reduced content of one or more nitride phases, such as a rare earth nitride (e.g., REN) phase, compared to a conventional corresponding halide material. The nitride phase may include cations of a metal element selected from the group consisting of Li, M, Me, and RE. In one aspect, the halide material may include a total content of nitride phases of no more than 7 wt % relative to the total weight of the halide material, such as no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, or no more than 0.5 wt % of the total content of nitride phases. In another aspect, the halide material may include a total content of nitride phases of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, or at least 0.05 wt % of the total content of nitride phases relative to the total weight of the halide material. In further aspects, the halide material may include a total content of nitride phases within a range including any of the minimum percentages and maximum percentages described herein. In a particular aspect, the halide material may be substantially free of at least one rare earth nitride phase and a Me metal nitride phase. In another particular aspect, when present in the halide material, the nitride phase may be substantially free of a phase including cations of the metal element RE or Me. In a more particular aspect, the halide material may be substantially free of a rare earth nitride phase and a Me metal nitride phase.

[0049] In one embodiment, the halide material may include a total content of impurity phases of no more than 16 wt %, such as no more than 15 wt %, no more than 14 wt %, no more than 13 wt %, no more than 12 wt %, no more than 10 wt %, no more than 9 wt %, no more than 8 wt %, no more than 7 wt %, such as no more than 6 wt %, no more than 5 wt %, no more than 4 wt %, no more than 3 wt %, no more than 2 wt %, no more than 1 wt %, no more than 0.5 wt %, no more than 0.3 wt %, or no more than 0.1 wt % relative to the total weight of the halide material. In another aspect, the halide material may include a total content of impurity phases of at least 0.0001 wt % relative to the total weight of the halide material, such as at least 0.0005 wt %, at least 0.001 wt %, at least 0.005 wt %, at least 0.01 wt %, or at least 0.05 wt % relative to the total weight of the halide material. In further aspects, the halide material can include a total content of impurity phases within a range including any of the minimum and maximum percentages described herein.

[0050] In certain embodiments, the halide material may be substantially free of binary halide phases, ternary halide phases, oxynitride phases, and oxyhalide phases. In more specific embodiments, the halide material may consist essentially of a single phase. For example, the halide material may consist of the formula Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p-q Br u F p I q ) 6-x+y*(k-3) The indicated phase and impurity phase composition, wherein the total content of the impurity phase may be at most 0.5 mol % or at most 0.3 mol %.

[0051] In one embodiment, the halide material may include specific crystalline structural features that may contribute to the improved properties of the halide material. The crystalline structural features may include a crystal system, a lattice system, a space group, one or more unit cell parameters, including unit cell volume, values ​​of a, b, c, or any combination thereof, the number of atoms within the unit cell, the stacking order, atomic vacancies, occupancy of vacancies, or any combination thereof.

[0052] In one embodiment, the halide material may include a crystalline structure of a monoclinic, trigonal, hexagonal or orthorhombic crystal system. In a specific embodiment, the halide material may include a crystalline structure represented by a space group of a monoclinic crystal system. In a specific example, the halide material may include a crystalline structure represented by a C2 / m space group.

[0053] In another specific embodiment, the halide material may include a crystalline structure represented by a space group of a rhombohedral lattice system, including R3, R32, R3m, R3c, or In a specific example, the halide material may have a space group consisting of The space group represents the crystal structure.

[0054] In another specific embodiment, the halide material may include a crystalline structure represented by a space group of a hexagonal crystal system. The hexagonal crystal system includes 27 space groups, including P6, P61, P65, P62, P64, P63, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc. For example, the halide material may include a crystalline structure represented by any of the space groups of the hexagonal crystal system. In a specific example, the halide material may include a crystalline structure represented by P63 / mcm. In another specific example, the halide material may include a crystalline structure represented by the P63 / mmc space group.

[0055] In certain embodiments, the halide material may include mixed crystalline mesophases, including multiple crystalline mesophases integrated at the atomic level, at the nanodomain level, or both. The nearest atomic distance is typically less than 0.5 nm, and the nanodomain may have a larger size than the nearest atomic distance, such as greater than 1 nm. In one aspect, the halide material may include a first crystalline phase having a first crystalline structure represented by a first space group and a second crystalline phase having a different second crystalline structure represented by a second space group.

[0056] In certain embodiments, the halide material may include a first crystalline mesophase having a first crystalline structure represented by a space group of a rhombohedral lattice system and a second crystalline mesophase represented by a space group of a monoclinic crystalline system, such as C2 / m. In another specific example, the halide material may include a third crystalline mesophase having a different crystalline structure. In a more specific example, the third crystalline mesophase may be represented by or express.

[0057] For example, the first crystalline mesophase may have a first crystalline structure represented by a space group of a hexagonal crystal system, and the second crystalline mesophase may have a second crystalline structure represented by a space group of a trigonal crystal system or an orthorhombic crystal structure. In a specific example, the second crystalline-mesophase may have a first crystalline structure represented by a space group of a hexagonal crystal system or an orthorhombic crystal structure. In another specific example, the second phase may have a second crystalline structure represented by a space group of Pnma. In a more specific example, the halide material may include a first crystalline mesophase having a first crystalline structure represented by a space group of P63 / mcm or P63 / mmc and a second crystalline structure represented by a space group of Pnma. Or a second crystalline mesophase of a second crystalline structure represented by Pnma.

[0058] In one embodiment, the halide material may include a crystalline structure including a unit cell that is smaller than that of Li3YBr6. In a particular aspect, the halide material may include a crystalline structure similar to Li3YBr6 but having a smaller unit cell volume. In another particular aspect, the halide material may include a powder X-ray diffraction (XRD) pattern wherein peaks of the halide material are shifted to higher angles compared to corresponding peaks of the powder diffraction pattern of Li3YBr6. See Figure 1A , shows the powder XRD patterns of representative halide materials Li3YBr3Cl3 and Li3YBr4Cl2 and Li3YBr6 measured with Cu K-α radiation. Compared with Li3YBr6, the corresponding peaks of Li3YBr3Cl3 and Li3YBr4Cl2 are shifted to larger 2θ values.

[0059] In another embodiment, the halide material may include a crystalline structure similar to Li3YCl6 but with a larger unit cell volume. In a specific example, the halide material may include a powder X-ray diffraction (XRD) pattern in which the peaks of the halide material are shifted to smaller angles compared to corresponding peaks of the powder diffraction pattern of Li3YCl6. Figure 1B , shows the powder XRD patterns of representative halide materials Li3YBr2Cl4 and Li3YBr1Cl5 and Li3YCl6 measured with Cu K-α radiation. The corresponding peak of Li3YBr1Cl5 is shifted to a smaller 2θ value compared to Li3YCl6. The XRD pattern of Li3YBr4Cl2 may indicate that the halide includes a mixed intermediate phase.

[0060] In a particular example, the halide material may include an XRD pattern measured with Cu K-alpha radiation including at least two peaks in the 2θ range of 13° to 15°. Figure 2 , showing that Li 3-x Y(Cl 1-u Br u ) 6-x Cu K-α XRD patterns of three samples. Sample 202 with u of 0.59±0.03 shows one peak in the 2θ range of 13° to 15°. Samples 204 and 206 with u of 0.38±0.03 and 0.31±0.03, respectively, show two peaks in the 2θ range of 13° to 15°.

[0061] In another embodiment, the halide material may include a specific average diffraction crystallite size, which may promote improved properties of the halide material. The average diffraction crystallite size may also be referred to as the coherent X-ray scattering domain size and is determined using X-ray diffraction analysis of the halide-based material and the Schrerrer equation L = (Kλ) / (βcosθ), where L represents the average diffraction crystallite size, where K is a dimensionless shape factor, whose value is close to unity and has a typical value of 0.9 to 1; λ is the X-ray wavelength; β is the line broadening at half the maximum intensity (FWHM) after subtracting the instrumental line broadening, in radians; and θ is the Bragg angle.

[0062] In one aspect, the halide material may include an average diffraction crystallite size of at least 20 nm, at least 25 nm, at least 30 nm, at least 35 nm, or at least 40 nm. In another aspect, the halide material may include an average diffraction crystallite size of at most 500 nm, at most 400 nm, at most 300 nm, at most 200 nm, or at most 100 nm. In further aspects, the halide material may include an average diffraction crystallite size within a range including any of the minimum and maximum values ​​described herein.

[0063] In one embodiment, the solid electrolyte material may include a halide material that includes a specific amount of Cl that can promote improved properties of the halide material and the solid electrolyte material. In one aspect, (1-upq) may be at least 0.12, at least 0.15, at least 0.17, at least 0.20, at least 0.23, at least 0.25, at least 0.27, at least 0.29, at least 0.33, at least 0.36, at least 0.43, at least 0.48, at least 0.50, at least 0.54, or at least 0.58. In another aspect, (1-upq) may be at most 0.99, at most 0.97, such as at most 0.92, at most 0.87, at most 0.83, at most 0.80, at most 0.77, at most 0.75, at most 0.70, or at most 0.66. In further aspects, (1-upq) can be within a range including any of the minimum and maximum values ​​noted herein.

[0064] In certain embodiments, the solid electrolyte material may include Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p- q Br u F p I q ) 6-x+y*(k-3), wherein u may be greater than 0. More specifically, the halide material may include a specific amount of Br, which may promote the improved properties of the halide material. In one aspect, u may be at least 0.1, such as at least 0.12, at least 0.15, at least 0.17, at least 0.2, at least 0.23, at least 0.25, at least 0.27, at least 0.29, at least 0.32, or at least 0.34. In another aspect, u may be at most 0.85, at most 0.83, at most 0.8, at most 0.77, at most 0.75, at most 0.7, at most 0.67, at most 0.65, at most 0.62, at most 0.6, at most 0.57, at most 0.54, at most 0.52, at most 0.49, at most 0.45, or at most 0.42. In another aspect, u may be within the range of any one of the minimum and maximum values ​​described herein.

[0065] In another embodiment, the halide material can include an amount of Cl to an amount of Br in a specific ratio ((1-upq) / u), which can promote improved properties of the halide material. In one aspect, the ratio of (1-upq) / u can be at least 0.03, such as at least 0.06, at least 0.1, at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 1.0, at least 1.2, at least 1.3, at least 1.4, at least 1.5, at least 1.6, at least 1.7, at least 1.8, at least 1.9, or at least 2.0. In another aspect, the ratio of (1-upq) / u can be no greater than 9, no greater than 8.6, no greater than 8.3, no greater than 8, no greater than 7.7, no greater than 7.4, no greater than 7, no greater than 6.5, no greater than 6.2, no greater than 6, no greater than 5.5, no greater than 5, no greater than 4, no greater than 3, no greater than 2, or no greater than 1.4. In additional aspects, the ratio of (1-upq) / u can be within a range including any of the minimum and maximum values ​​described herein.

[0066] In other embodiments, the halide material may include halide anions consisting of Cl and Br. In a specific example, the halide material may consist of Li 3-x RE 1-y Me k y (Cl 1-u Br u ) 6-x+y*(k-3) , where u>0, and in certain applications, 0.08<=u<=0.67. In another example, the halide material may be Li 3-x Y(Cl 1-u Br u ) 6-xIt is shown that, and in a particular application, u can be at least 0.55 or at most 0.45. In a particular embodiment, 0.2 <= u <= 0.45.

[0067] After reading this disclosure, those skilled in the art will understand that the properties of the halide materials of the embodiments herein can be adjusted or tuned by carefully controlling the amount of one or more of the halide anions in the halide anion, their ratios, the crystal structure of the halide material, or any combination thereof. In one embodiment, when both Br and Cl are present, by carefully controlling the amount of Br and / or Cl and / or the ratio of (1 - u - p - q) / u, the halide material can include a layered crystal structure similar to Li3YBr6, improved ionic conductivity compared to Li3YCl6, and improved electrochemical thermodynamic stability and similar mechanical deformability compared to Li3YBr6. In another embodiment, the halide material can include Br and Cl and have a crystal structure including a mixed crystal intermediate phase described in the embodiments herein. The halide material can have improved ionic conductivity compared to Li3YCl6 and improved electrochemical thermodynamic stability compared to Li3YBr6.

[0068] In another embodiment, when 0 < u < 0.33, the halide material can include a crystal structure including a hexagonal / trigonal crystal structure similar to Li3YCl6, improved ionic conductivity and mechanical deformability compared to Li3YCl6, particularly at lower temperatures (i.e., less than 200 °C), and improved electrochemical thermodynamic stability compared to Li3YBr6. Due to the lower density compared to Li3YBr6, this halide material can be particularly suitable for certain applications, such as manufacturing low-weight battery packs.

[0069] In a particular embodiment, the halide material is composed of Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p-q Br u F p I q ) 6-x+y*(k-3)It is shown that p can be greater than 0. More specifically, the halide material can include a specific amount of F, which can promote improved properties of the halide material. In one aspect, p can be at least 0.04, such as at least 0.06, at least 0.08, at least 0.09, at least 0.10, at least 0.12, at least 0.14, at least 0.15, at least 0.17, at least 0.2 or at least 0.22. In another aspect, p can be at most 0.33, such as at most 0.31, at most 0.29, at most 0.27, at most 0.25, at most 0.22, at most 0.20, at most 0.18, at most 0.16, at most 0.14, at most 0.12 or at most 0.10. In another aspect, p can be in a range including any of the minimum and maximum values described herein.

[0070] Examples of the halide material can include Li3Me 3+ Cl 6(1-p) F 6p , where 0 < p < 0.58. In a specific example, Me can include In, or more specifically, can consist of In. The solid solution of the chloride-fluoride halide phase can have a crystal structure represented by the space group C2 / m and has improved ionic conductivity compared to Li3InF6 and Li3InCl6.

[0071] In another embodiment, the halide material can include a specific ratio ((1 - u - p - q) / p) of the amount of Cl to the amount of Br, which can promote improved properties of the halide material. In one aspect, the ratio of (1 - u - p - q) / p can be at least 0.5, such as at least 0.7, at least 0.9, at least 1.0, at least 1.2, at least 1.4, at least 1.5, at least 1.6, at least 1.7, at least 1.8, at least 1.9, at least 2.0, at least 2.2, at least 2.4, at least 2.6, at least 2.8, at least 3.0, at least 3.2, at least 3.4 or at least 3.6. In another aspect, the ratio of (1 - u - p - q) / p can be no greater than 24, such as no greater than 21, no greater than 19, no greater than 17, no greater than 15, no greater than 13, no greater than 12, no greater than 11, no greater than 9, no greater than 8, no greater than 6 or no greater than 5. In a further aspect, the ratio of (1 - u - p - q) / p can be in a range including any of the minimum and maximum values described herein.

[0072] In one embodiment, the halide material can be represented by the formula Li a M a’ Me b Me’ b’ X c X’ c’M may be at least one alkali metal element other than Li, as described in the above embodiment. In a specific example, M may be at least one element selected from the group consisting of Na, K, and Cs.

[0073] Me can be at least one element from the group consisting of IIIB group elements, IVB group elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, In, Sn, Pb, Bi, Sb, Mg, Ca, Ga and Ge, as described in the embodiments of this article. In a specific example, Me can be RE as discussed in the embodiments of this article.

[0074] Me' is different from Me and may be at least one element from the group consisting of IIIB group elements, IVB group elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, In, Sn, Pb, Bi, Sb, Mg, Ca, Ga, and Ge. In a specific example, Me' may be at least one element from rare earth elements, Zr, and Fe.

[0075] X may be at least one halogen, and X' may be at least one halogen other than X. In a specific example, X may be at least one element of Cl, Br, and F. In another specific case, X' may be at least one element of Br and F.

[0076] In another embodiment, the solid electrolyte material may include Li a M a’ Me b Me' b’ X c X' c’ In another embodiment, the solid electrolyte material may include a halide material represented by wherein a≥a', b≥b', and c≥c'. Specifically, the halide material may include low levels of one or more impurities, as described in the embodiments herein. In yet another embodiment, the solid electrolyte material may include a Li a M a’ Me b Me' b’ X c X' c’ Representing a halide material, wherein anions of the halide material may be in a single phase.

[0077] In one embodiment, the halide material may include at least 4 elements. In other embodiments, the halide material may have a crystallographic phase transition, which can be induced by adjusting the stoichiometric ratio of two or more of the elements. In a specific embodiment, the stoichiometric ratio of the elements at the same site of the crystalline structure can be adjusted so that the halide material can have improved properties, including, for example, ionic conductivity, electrochemical stability, conformality, etc. or any combination thereof. After reading this disclosure, a person skilled in the art will understand that Li and M can be present at the same crystallization site; Me and Me' can be present at the same crystallization site, and X and X' can be present at the same crystallization site. In one example, the stoichiometric ratio of Me and Me', or the stoichiometric ratio of Li and M, or the stoichiometric ratio of X and X', or any combination thereof, can be adjusted to improve one or more properties of the halide material. In a specific example, X can be Cl, X' can be Br, and the stoichiometric ratio of X and X' can be adjusted to improve the ionic conductivity of the halide material, such as Li + In another specific example, M can be Na, and the stoichiometric ratio of Li and M can be adjusted to improve ionic conductivity. In yet another example, Me can be Y, and Me' can be In, and the stoichiometric ratio of Me to Me' can be adjusted to improve the ionic conductivity of the halide material.

[0078] The halide material may have a crystallographic phase transition boundary on a composition phase diagram. In the present disclosure, the crystallographic phase transition boundary may also be referred to as a morphotropic phase boundary (MPB). In one embodiment, a crystallographic phase transition may be induced by changing the stoichiometric ratio of Me and Me'. Specifically, when b / (b+b') changes from (b / (b+b')) t *0.84 to (b / (b+b')) t * Within the stoichiometric range of 1.16, halide materials can have phase transitions where (b / (b+b')) t Corresponding to a crystallographic phase transition boundary on a composition phase diagram at room temperature (i.e., 22° C.). In a particular aspect, b>b'>0, c≥0, c'≥0, and (c+c')>0. In another aspect, at least one of Me and Me' may include RE, as discussed in the embodiments of the present disclosure. In a particular aspect, Me may include RE, and Me' may include another tetravalent or trivalent element. In a more particular aspect, Me may include Y, and Me' may include Zr. Even more specifically, Me may be Y, and Me' may be Zr.

[0079] In one embodiment, the halide material may have a crystallographic phase transition, which can be induced by changing the stoichiometric ratio of X and X'. Specifically, when c / (c+c') changes from (c / (c+c')) to (c / (c+c')) on the composition phase diagram, t *0.84 to (c / (c+c')) t * Within the stoichiometric range of 1.16, halide materials can have phase transitions where (c / (c+c')) t Corresponding to a crystallographic phase transition boundary on a composition phase diagram at room temperature (i.e., 22° C.). In a particular aspect, c≥c'>0, b≥0, b'≥0, and (b+b')>0. In another particular aspect, X may include Cl, and X' may include Br. In a more particular aspect, X may be Cl, and X' may be Br. In another particular aspect, at least one of M and M' may be RE, as discussed in the embodiments of the present disclosure. In an even more particular aspect, one of M and M' may be Y.

[0080] In another embodiment, the halide material may have a crystallographic phase transition that can be induced by a change in the stoichiometric ratio of Li and M. Specifically, when a / (a+a') changes from (a / (a+a')) t *0.84 to (a / (a+a')) t *Halide materials can have phase transitions within the stoichiometric range of 1.16, where (a / (a+a')) t Corresponding to the crystallographic phase transition boundary on the composition phase diagram at room temperature (ie, 22° C.). In another embodiment, a>0 and a'>0. In a specific embodiment, a>a'. In another specific embodiment, M may include Na. In a more specific embodiment, M may be Na.

[0081] In one embodiment, the halide material may have a crystallographic phase transition, including a transition across a crystallographic phase transition boundary. In another embodiment, the crystallographic phase transition may include a change in one or more properties of the crystalline structure. Examples of properties of the crystalline structure may include the volume of the unit cell, the space group, the crystal system, one or more features of the XRD pattern, or any combination thereof.

[0082] In one embodiment, the halide material may include a monoclinic, trigonal, hexagonal or orthorhombic crystal system, and the crystallographic phase transition may include a transition from one crystal system to another crystal system. In other embodiments, the halide material may include a crystallographic phase transition, including a transition from a layered structure to a non-layered structure. For example, the crystallographic phase transition may include a crystal system transition from monoclinic to trigonal. In other embodiments, the crystallographic phase transition may include a transition from a C2 / m space group or an R-3m space group to a P-3m1 or Pnma space group. In yet another embodiment, the crystallographic phase transition may include a transition from a cubic close-packed structure to a hexagonal close-packed structure.

[0083] In other embodiments, the crystallographic phase transition may include a transition from a non-laminated structure to another non-laminated structure. In yet another embodiment, the crystallographic phase transition may include a transition from a non-laminated structure to a lamellar structure. In a specific example, the crystallographic phase transition may include a transition from R3c to R3m. In another specific example, the crystallographic phase transition may include a transition from a P-3m1 or Pnma space group to a C2 / m space group or an R-3m space group.

[0084] In other embodiments, when the halide material has a crystallographic phase transition, certain crystalline structural characteristics may not change. For example, the XRD pattern of the halide material may include a phase transition feature that indicates an increase or decrease in unit cell volume, while certain other XRD features may not change. In a specific example, the halide material may include a crystallographic phase transition and an XRD pattern including the absence of a peak between 5° and 13° 2θ.

[0085] In one embodiment, the halide material may have a phase change without changing the elements of the halide material. As described above, the stoichiometric ratio of the elements may be adjusted. The ratio of the elements may be expressed in mole % or atomic %.

[0086] In one embodiment, the halide material can be stoichiometric. In another embodiment, the halide material can be non-stoichiometric. For example, the halide material can include vacancies that replace some of the elements in the composition and maintain the electrical neutrality of the phase under this range.

[0087] In one embodiment, the halide material may be composed of Li a-f M a’ RE b Me' k b’ (Cl c Br c’ ) 6-f+(k-3)*b= 3, -1≤f≤1, (c+c') = 1, and (b+b') = 1. In certain embodiments, the halide material may include X and X', wherein c>c' and 0.63≤c / (c+c')≤0.98.

[0088] In another embodiment, the halide material may be composed of Li 3-f RE b Me' k b’ (Cl c Br c’ ) 6-f+(k-3)*b’ = 0.001, (c+c') = 1, (b+b') = 1, b>0, and b'≥0. In certain aspects, b' may be 0. Specific examples of halide materials may include Li3Y1(Cl c Br c’ )6, wherein 0.63≤c / (c+c')≤0.87. In another aspect, b>b'>0. Specific examples of halide materials may include Li 3-f Y b Me' k b’ (Cl c Br c’ ) 6-f+(k-3)*b’ , wherein k=3 or 4 and 0.65≤c / (c+c')≤0.98. More specific examples of the halide material may include Li 3-b’ Y b Zr b’ (Cl c Br c’ )6, wherein 0.72≤c / (c+c')≤0.98. Another more specific example of the halide material may include Li 3-f Y b Yb b’ (Cl c Br c’ ) 6-f , wherein 0.65≤c / (c+c')≤0.89. Another more specific example of the halide material may include Li 3-f Y b In b’ (Cl c Br c’ ) 6-f , where 0.69≤c / (c+c')≤0.95.

[0089] More specific examples of halide materials may include Li3Y1(Cl 0.8 Br 0.2 )6、Li3Y1(Cl 0.67 Br 0.33)6、Li3Y1(Cl 0.79 Br 0.21 )6、Li3Y1(Cl 0.62 Br 0.38 6. Li 2.95 (Y 0.95 Zr 0.05 )(Cl 0.9 Br 0.1 )6、Li3(Y 0.95 Yb 0.05 )1(Cl 0.83 Br 0.17 )6、Li3(Y 0.95 In 0.05 )1(Cl 0.9 Br 0.1 )6.

[0090] Figure 8 Including Cl concentration in mol% at room temperature and Li3YCl c Br c As shown in the figure, Cl is 75 mol% at the crystallographic phase transition boundary (at Figure 8 %. In the embodiment of the present invention, the halide material is represented by a vertical dotted line and is referred to as MPB. Before the mole % of Cl increases to 75 mole %, the halide material may have a crystalline structure similar to the layered crystalline structure of LYB. When the mole % of Cl is at least 75 mole %, the halide material may have a crystalline structure similar to the non-layered crystalline structure of LYC.

[0091] like Figure 8 As shown, when the concentration of Cl increases to about 63 mol %, the ionic conductivity of the halide material can increase to about 2 ms / cm. As further shown, when the concentration of Cl is adjusted to about 65 mol % (in Figure 8 is referred to as "LYBC-65") and 80 mol% (in Figure 8 When the concentration of Cl is adjusted to a range of 63 mol % to 87 mol %, the ionic conductivity of the halide material can be at least 2.08 mS / cm or at least 2.20 mS / cm, which is unexpectedly higher than the ionic conductivity of LYB.

[0092] LYB has a layered crystalline structure, which is beneficial for LYB to have a higher ionic conductivity than LYC having a non-layered crystalline structure. When the concentration of Cl is in the range of 63 mol% to less than 75 mol%, the crystalline structure of the halide material may be deformed compared to the layered structure of LYB, rather than a typical layered structure. When the concentration of Cl is 75 mol% to 87 mol%, the halide material has a non-layered crystalline structure. Therefore, unexpectedly, when the halide material has a crystalline structure that is less favorable than the layered structure of LYB to have a higher ionic conductivity, the halide material may have an ionic conductivity significantly higher than the ionic conductivity of LYB.

[0093] Fig. 9A Including representative halide materials Li3Y(Cl 0.79 Br 0.21 )6 measured with Cu K-α radiation, the powder XRD pattern being overlaid with the XRD pattern of Li3YCl6. The XRD peaks of the representative halide materials are shifted to smaller angles compared to the corresponding peaks of the powder XRD pattern of Li3YCl6. Fig. 9B , representative halide materials Li3Y(Cl 0.67 Br 0.33 )6 measured with Cu K-α radiation is combined with the XRD pattern of Li3YBr6. The corresponding peaks of the representative halide materials are shifted to larger 2θ values ​​compared to Li3YBr6. It can be observed that Li3Y(Cl 0.67 Br 0.33 )6 is a single-phase halide material.

[0094] In one embodiment, the halide material may be composed of Li 3-f RE b Me' k b’ X 6-f+(k-3)*b’ = , where -1≤f≤1 and (b+b')=1. In a particular aspect, k=3. For example, Me may include In. In another particular aspect, RE may include Y. In yet another particular aspect, 0.67≤b / (b+b')≤0.93. Specific examples of halide materials may include Li 3-f Y b In b’ X 6-f .

[0095] In another embodiment, the halide material may be composed of Li a M a’REX6 represents, wherein a>a'>0, (a+a')=3 and 0.942≤a / (a+a')≤0.958. In one aspect, M may include Na. In another aspect, RE may include Y. In another aspect, X may include Cl. In a specific aspect, the halide material may be Li a Na a’ YCl6, and 0.942≤a / (a+a')≤0.958.

[0096] More specific examples of halide materials may include Li3(Y 0.85 In 0.15 )Cl6 and (Li 0.955 Na 0.045 )3YCl6.

[0097] In one embodiment, the halide material may be of the formula Li a M a’ RE b Me' b’ Cl c X' c’ Represents, wherein Me may have a smaller ionic radius than RE. In a particular aspect, RE may be Y. On the one hand, Me with a smaller ionic radius can promote the crystallographic phase transition of the halide material from a non-layered structure (when b'=0) to a layered crystalline structure. For example, the crystallographic phase transition may include a transition from Pnma or P-3m1 to C2 / m or C2 / c. In another example, the crystallographic phase transition may include a transition from orthorhombic to monoclinic crystallography. In another aspect, the crystallographic phase transition can be controlled by adjusting the stoichiometric ratio of RE and Me. Specifically, with the time b / (b+b')>(b / (b+b')) t *1.16 and b / (b+b')<(b / (b+b')) t *0.84, when (b / (b+b')) t *0.84 t * 1.16, the halide material may have significantly improved properties, including, for example, ionic conductivity. Examples of Me may include divalent elements, trivalent elements, tetravalent elements, or any combination thereof. Specific examples of Me may include Yb, SC, In, Zr, Ga, or any combination thereof.

[0098] In one embodiment, the halide material may be of the formula Li a M a’ RE b Me' b’ Cl c X' c’ ​In other aspects, when c'=0, X' with a larger ionic radius can promote the crystallographic phase transition from a non-layered structure to a layered crystalline structure of the halide material by adjusting the stoichiometric ratio of Cl and X'. Specifically, when (c / (c+c')) t *0.84>c / (c+c') and c / (c+c')>(b / (b+b')) t *1.16, when (c / (c+c')) t *0.84 <c / (c+c’)<(b / (b+b’)) t *1.16, the halide material can have significantly improved properties such as ionic conductivity.

[0099] In another embodiment, the halide material may be of the formula Li a M a’ RE b Me' b’ Cl c X' c’ Represents, wherein M may have an ionic radius larger than Li. In one aspect, M may include Na, K, Cs, Cu, or a combination thereof. In a particular aspect, RE may be Y. In another aspect, when a'=0, M with a larger ionic radius may promote a crystallographic phase transition from a non-layered structure of a halide material to a layered crystalline structure or another non-layered structure. For example, a crystallographic phase transition may include a transition from Pnma or P-3m1 to C2 / m or C2 / c. In another example, the transition may include a transition from orthorhombic to cubic potassium cryolite or a monoclinic crystalline structure. In a particular aspect, the transition may be controlled by adjusting the stoichiometric ratio of Li and M. Specifically, compared to when (a / (a+a')) t *0.84>a / (a+a')and a / (a+a')>(a / (a+a')) t *1.16, when (a / (a+a')) t *0.84 t *1.16, the halide material may have significantly improved properties, such as ionic conductivity, electrochemical stability, conformability, or any combination thereof.

[0100] In one embodiment, the halide material may be of the formula Li a M a’ RE b Me' b’ Cl c X' c’ ​Represents, wherein Me may have an ionic radius larger than RE. In a particular aspect, RE may be Y. On the one hand, Me having a larger ionic radius may promote the crystallographic phase transition of the halide material from a non-layered structure (when b'=0) to a layered crystalline structure or another non-layered crystalline structure. For example, the crystallographic phase transition may include a transition from Pnma or P-3m1 to C2 / m or C2 / c. In another example, the crystallographic phase transition may include a transition from orthorhombic to monoclinic crystallography. In another aspect, the crystallographic phase transition may be controlled by adjusting the stoichiometric ratio of RE and Me. Specifically, with the time b / (b+b')>(b / (b+b')) t *1.16 and b / (b+b')<(b / (b+b')) t *0.84, when (b / (b+b')) t *0.84 t * 1.16, the halide material may have significantly improved properties, including, for example, ionic conductivity. Examples of Me may include divalent elements, trivalent elements, tetravalent elements, or any combination thereof. Specific examples of Me may include Bi, La, Ce, Gd, or any combination thereof.

[0101] In one embodiment, the halide material may be of the formula Li a M a’ RE b Me' b’ Cl c X' c’ In other aspects, when c'=0, X' with a smaller ionic radius can promote the crystallographic phase transition from a non-layered structure of the halide material to a layered crystalline structure or another non-layered crystalline structure by adjusting the stoichiometric ratio of Cl and X'. Specifically, when (c / (c+c')) t *0.84>c / (c+c') and c / (c+c')>(b / (b+b')) t *1.16, when (c / (c+c')) t *0.84 <c / (c+c’)<(b / (b+b’)) t *1.16, the halide material may have significantly improved properties, such as ionic conductivity, electrochemical stability, conformability, or any combination thereof.

[0102] In one embodiment, the crystallographic phase transition boundary can be determined as follows, using the Li 3-x*k (Y 1-x Me k+ ​x )(Cl c Br c’ )6 is taken as an example. The MBP of the halide material can be expressed according to the formula [c / (c+c')] t =0.75+12*(δ*x) to determine, where Me k+ The ionic radius is r, where r = r_Y 3+ *(1-δ), where r_Y 3+ Yes 3+ Similarly, for halide materials having a crystallographic phase transition induced by tuning Li substitution by M or by tuning Me substitution by Me', the MPB can be determined.

[0103] In one embodiment, the halide material may include a crystalline phase within a specific band range, including a crystallographic phase transition boundary on a composition phase diagram. In one aspect, the band range may be represented by a concentration range of an element (such as one of Li and M, one of Me and Me', or one of X and X') of the halide material. For example, the halide material may have a crystallographic phase within an element concentration range of 0.84 to 1.16 times the element concentration at the crystallographic phase transition boundary. Specifically, the stoichiometric ratio of the elements can be adjusted to promote crystallographic phase transitions and improvements in the properties of the halide material. In particular aspects, the halide material may be substantially composed of a crystalline phase within a specific band range. For example, anions of the halide material may be present in the same phase. As discussed in the embodiments herein, the halide material may have a low content of impurities or may be substantially free of impurities. For example, the level of impurities may be lower than the detectable level using conventional detection methods. Thus, "consisting essentially of a single phase" is intended to mean that the halide material may include a low level of an impurity phase in addition to the main phase of the complex compound of the halide material; or the halide material may be free of the impurity phase. In the present disclosure, the impurity phase may also be referred to as a parasitic impurity phase.

[0104] In one embodiment, the halide material may include a specific density that may promote improved properties and / or performance of the solid electrolyte material. In one aspect, the density may be greater than 2.3 g / cm 3 , such as at least 2.5 g / cm 3 , at least 2.7g / cm 3 , at least 2.9g / cm 3 , at least 3.1g / cm 3 , at least 3.3g / cm 3 or at least 3.5g / cm 3 In another aspect, the halide material can have a carbon content of less than 3.8 g / cm 3 , such as not more than 3.5g / cm 3 , not more than 3.4g / cm3 , not more than 3.3g / cm 3 , or not more than 3.1g / cm 3 In another aspect, the halide material can have a density within a range including any of the minimum and maximum values ​​described herein. In a particular embodiment, the halide material can have a density less than the density of Li3YBr6 and greater than the density of Li3YCl6.

[0105] In one embodiment, compared with Li3YBr6, the halide material may have significantly improved thermodynamic electrochemical stability. In another embodiment, the halide material may include a thermodynamic electrochemical stability value, which may promote the improved properties of the solid electrolyte material. The thermodynamic electrochemical stability value may be determined as follows based on cyclic voltammetry or linear sweep voltammetry. The electrochemical cell may be made of three layers. The active layer (ie, the working electrode) may include a mixture of carbon and halide materials. The separator layer may be made of halide materials. The counter electrode layer may be made of indium metal or lithium-indium alloy. The voltage of the working electrode of the electrochemical cell relative to the counter electrode may gradually increase, and at the same time, the oxidation current may result in a peak or platform indicating electrolyte oxidation and be measured. The starting value of the peak can be obtained by linearly extrapolating the peak rise to the x-axis, and in volts. A 0.62V offset may be added to the starting value of the peak to obtain a thermodynamic electrochemical stability value and convert the indium counter electrode potential into a standard Li / Li+ potential.

[0106] In one aspect, the thermodynamic electrochemical stability value may be greater than 3.57 V, such as at least 3.60 V, at least 3.62 V, 3.65 V, or at least 3.71 V. In another aspect, the halide material may include a thermodynamic electrochemical stability value of no greater than 4.50 V, no greater than 4.30 V, no greater than 4.19 V, no greater than 4.15 V, no greater than 4.10 V, no greater than 3.85 V, no greater than 3.80 V, no greater than 3.75 V, or no greater than 3.71 V. In another aspect, the halide material may include a thermodynamic electrochemical stability value within a range including any of the minimum and maximum values ​​described herein.

[0107] In another embodiment, the halide material may include improved bulk ionic conductivity, including, for example, lithium ion conductivity, compared to conventional corresponding halide materials. The bulk ionic conductivity may be measured at room temperature (i.e., 22° C.). In one aspect, the ionic conductivity may be greater than 0.05 mS / cm, greater than 0.15 mS / cm, at least 0.3 mS / cm, at least 0.5 mS / cm, at least 0.8 mS / cm, at least 0.9 mS / cm, at least 1.1 mS / cm, at least 1.5 mS / cm, or at least 1.7 mS / cm. In another aspect, the halide material may include a bulk ionic conductivity of less than 4.5 mS / cm, less than 3.4 mS / cm, less than 2.8 mS / cm, less than 2.0 mS / cm, such as at most 1.9 mS / cm, at most 1.8 mS / cm, or at most 1.7 mS / cm measured at 22° C. In another aspect, the halide material can have an in-bulk ionic conductivity within a range including any of the minimum and maximum values ​​described herein.

[0108] In other embodiments, the electrolyte materials of the embodiments herein may have further improved ionic conductivity, particularly when the halide material has a crystalline phase within a specific band range, including a morphotropic phase transition boundary (MPB) in a crystallographic phase transition diagram. In one aspect, the halide material may have an ionic conductivity in the bulk of at least 1.8 mS / cm, at least 1.85 mS / cm, at least 1.87 mS / cm, at least 2.0 mS / cm, at least 2.08 mS / cm, or at least 2.45 mS / cm, as measured at 22°C. In another aspect, the halide material can comprise an in-bulk ionic conductivity of at most 6.5 mS / cm, at most 6.1 mS / cm, at most 5.8 mS / cm, at most 5.3 mS / cm, at most 5.1 mS / cm, at most 4.7 mS / cm, at most 4.4 mS / cm, at most 4.1 mS / cm, at most 3.9 mS / cm, at most 3.6 mS / cm, at most 3.2 mS / cm, at most 3.0 mS / cm, at most 2.8 mS / cm, or at most 2.5 mS / cm measured at 22° C. In another aspect, the halide material can have an in-bulk ionic conductivity within a range including any of the minimum and maximum values ​​recited herein.

[0109] As used herein, by applying electrochemical impedance spectroscopy to dense pellets formed by pressing electrolyte material powder, ionic conductivity in the bulk can be measured. The dense pellets can be sandwiched between stainless steel electrodes and can be measured at an isostatic pressure of about 300MPa. A sinusoidal voltage signal can be applied to the dense pellets at a frequency of 7MHz as low as 1Hz and an amplitude of 50mV. Ionic conductivity in the bulk can be measured at 22°C. In an embodiment, activation energy can be obtained to help understand certain properties of the electrolyte material, such as ionic conductivity in the bulk relative to temperature. For example, a lower activation energy can indicate a smaller change in ionic conductivity in the bulk with temperature. In order to determine the activation energy, ionic conductivity in the bulk can be measured at a temperature of 22°C to 150°C to generate an Arrhenius plot based on the equation IC(T)=A×exp(-Ea / RT), where A is a pre-exponential constant, Ea is an activation energy in eV, R is a universal constant for conversion degrees Kelvin in eV, and T is a temperature in degrees Kelvin. The slope of the line of the graph can be used to determine the activation energy. In certain embodiments, the activation energy may be in the range of 0.2 eV to 0.5 eV.

[0110] See also Figure 3 , a process 300 for forming a solid electrolyte material including a halide material is shown.

[0111] Process 300 is different from conventional solid-state synthesis for forming complex halide materials. Conventional processes utilize high-energy ball milling or directly heat a solid reactant mixture (e.g., a simple metal halide) at a temperature close to or below the melting point of the metal halide to perform a solid-state reaction. Because the probability of reacting a single isolated particle in the mixture decreases as the reaction proceeds, achieving 100.00% reaction completion will theoretically take an infinite amount of time. It is therefore understood that the reaction products produced by conventional solid-state synthesis based on high-energy ball milling have a higher concentration of impurities, such as simple metal halides (e.g., lithium halides and / or yttrium halides), due to the incomplete reaction of the simple metal halides.

[0112] It is further worth noting that the conventional synthesis of complex halides based on the ammonium halide route may not be suitable for forming complex metal halides. Metal halides are generally used as starting materials. Since some trivalent metal halides and tetravalent metal halides, especially rare earth halides, tend to form stable metal halide hydrates, it is difficult to completely remove water molecules from those hydrates. Increasing the temperature can lead to the formation of undesirable metal oxyhalides or metal hydrated oxyhalide compounds in higher concentrations. In addition, metal halide hydrates and metal oxyhalides, especially those including rare earth metals, are fairly stable compounds and are unlikely to form complex compound phases containing high concentrations of Li, such as Li3RE(OX)Cl3, where X is a halogen other than Cl. In addition, those complex compounds will not be stable and will likely decompose into simpler compounds.

[0113] The process described in the embodiments of the present disclosure overcomes the above-mentioned problems.

[0114] Process 300 can start with a mixture of starting materials that includes one or more metal compounds of Li, M, RE, Me or any combination thereof in a stoichiometric or non-stoichiometric ratio. The metal compound can be non-hygroscopic. Specifically, the starting material can include ammonium halides, NH4X, wherein X includes Cl, Br, I, F or any combination thereof. The starting material can also include an acid, such as hydrochloric acid or hydrobromic acid, to promote acidic synthesis in aqueous solutions, alcoholic solutions or other polar molecular liquid solutions.

[0115] In an exemplary embodiment, the metal compound may include an oxide, a carbonate, a sulfate, a hydrate, a hydroxide, an oxalate, an acetate, a nitrate, or any combination thereof. For example, the starting material may include Me2O k Oxides, including, for example, one or more rare earth oxides in rare earth oxides. In another example, hydroxides or carbonates, such as lithium carbonate, sodium carbonate, cesium carbonate, Fe(OH)2 or Fe(CO3), or any combination thereof, can be used.

[0116] See also Figure 3 , process 300 may include forming an ammonium-containing halide from a starting material, as shown at block 302. Exemplary ammonium-containing halides may include (NH4) z RE 1-y Me k y (Cl 1-u-p-q Br u F p I q ) 3+z+y*(k-3) 、(NH4) z RE 1-y Me ky (Cl 1- u Br u ) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (Cl 1-p F p ) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (Cl) 3+z+y*(k-3) 、(NH4) z RE 1- y Me k y (Br) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (I) 3+z+y*(k-3) Or a combination thereof. In a particular embodiment, 0.33<=z<=5. In each case, the formation of the ammonium-containing metal halide material can be carried out in a liquid medium such as an acid solution. Exemplary acids can include hydrochloric acid, hydrobromic acid, hydrofluoric acid, hydroiodic acid, or any combination thereof. In other cases, the formation of the ammonium-containing metal halide material can be carried out under specific drying conditions.

[0117] In one embodiment, the formation of the ammonium-containing metal halide material can be carried out at a temperature of up to 250° C. For example, the temperature can be at least 20° C., at least 40° C., at least 50° C., at least 70° C., at least 90° C., at least 110° C., or at least 140° C. In another example, the temperature can be no greater than 200° C., no greater than 180° C., no greater than 160° C., or no greater than 140° C. In further examples, the ammonium-containing metal halide can be formed at a temperature within a range including any of the minimum and maximum values ​​described herein.

[0118] In an exemplary synthesis of a halide material, an ammonium-containing metal halide may include two metal cations and a halide anion and may be used to form the halide material of the embodiments herein. In at least one exemplary synthesis process, an ammonium-containing metal halide may be treated to form a metal halide, and a reaction between metal halides having different halide anions may be performed to form the halide material of the embodiments herein. For example, Li3YBr6 and Li3YCl6 may be formed separately and then mixed to form Li3YCl6 described in detail below. 6(1-u) Br 6uThe following reaction may occur in a mixture of starting materials including Li2CO3, Y2O3, HBr, NH4Br and H2O to form Li3YBr6.

[0119] 3*Li2CO3+Y2O3+12*HBr+10*H2O→2*YBr3(H2O)8+6*LiBr+3*CO2

[0120] 6*NH4Br+2*YBr3(H2O)8+6*LiBr→2*(NH4)3YBr6+6*LiBr+16*H2O

[0121] The above reaction mixture may be heated at 140° C. under reduced pressure to remove moisture and promote the subsequent solid-state reaction.

[0122] 2*(NH4)3YBr6+6*LiBr→2*Li3YBr6+6*NH4Br

[0123] The reaction mixture can be further heated at 550°C to sublime the ammonium bromide.

[0124] Li3YCl6 can be formed from a mixture of starting materials including Y2O3, Li2CO3, H2O, NH4Cl and HCl as follows.

[0125] Y2O3+3*Li2CO3+10*H2O+12*HCl→2*YCl3(H2O)8+6*LiCl+3*CO2

[0126] 2*YCl3(H2O)8+6*LiCl+6*NH4Cl→2*(NH4)3YCl6+6*LiCl+16*H2O

[0127] The reaction mixture may be heated at 140°C under reduced pressure to remove moisture and promote the subsequent solid-state reaction.

[0128] 2*(NH4)3YC16+6*LiCl→2*Li3YCl6+6*NH4C1

[0129] The reaction mixture can be further heated at 550°C to sublime the ammonium chloride.

[0130] After formation, the Li3YCl6 phase and the Li3YBr6 phase may be mixed in a stoichiometric ratio, and a solid-state reaction may be performed under dry conditions in an inert atmosphere such as nitrogen to form Li3YCl (1-u)*6 Br 6*u .

[0131] In some cases, Li3Y(Cl 1-u Br u)6 The mass of the material can be formed by a solid phase reaction, and grinding can be carried out in a neutral atmosphere of N2 or Ar to form a powder.

[0132] In other embodiments, ammonium-containing metal halides may be formed to facilitate the formation of halide materials of embodiments herein. c X' c As an example, the halide materials represented can be used to form (NH3)3Li3YBr9 and (NH3)3Li3YCl9 in aqueous solution, respectively, using the raw materials described in the embodiments of this article. In one aspect, the solutions can be mixed and dried at 100°C to 170°C to allow moisture and acid to evaporate. In a particular aspect, the solid state reaction of the halide compounds and the sublimation of NH3Cl and NH3Br from the charge can be carried out in parallel at a relatively low temperature. For example, a flux having LiCl and NH4Cl can be formed at a temperature below the sublimation point of NH4Cl. NH4Br can be sublimated at a temperature above 350°C. Without wishing to be bound by any theory, it should be noted that the presence of ammonium halide can allow the formation of Li3YCl at a relatively low temperature c X' c’ final phase, which helps to form a uniform c / c' ratio throughout the final phase, which can be advantageous over the synthesis of halide powders using conventional solid-state reactions of LYC and LYB powders, because conventional solid-state synthesis typically results in a relatively high dispersion of c / c' ratios in the final product, such that the final product may have multiple phases including different ratios of c / c'.

[0133] In another aspect, after the sublimation of ammonium, cooling can be performed. Specifically, cooling should be carefully controlled to avoid segregation of the crystalline phase of the halide material. In a particular embodiment, the cooling rate can be up to 200°C / hour, such as greater than 40°C / hour, at least 60°C / hour, at least 70°C / hour, at least 90°C / hour, or at least 100°C / hour, at least 150°C / hour, or at least 180°C / hour. Fig.10 Including the formation of halide material Li3Y(C 0.65 Br 0.35 )6, which includes a specific accelerated cooling step. In the process shown, after forming and combining the ammonium-containing LYB and ammonium-containing LYC solutions, drying the reaction mixture is carried out at about 120°C. The reaction mixture is heated to about 550°C to carry out a solid-state reaction and sublimate the ammonium in parallel. Accelerated cooling is performed after sublimation. Halide material Li3YC 4.5 Br 1.5 With single phase.

[0134] It will be appreciated by those skilled in the art that additional alkali metal compounds such as Na2CO3 or NaCl may be added to the mixture of starting materials to partially replace Li in the halide material. Similarly, a compound of another RE or Me metal (such as Fe2O3) may also be added to the mixture to replace Y in the halide material.

[0135] In applications, the reaction mixture may be filtered to remove larger particles from the solid state reaction. Larger particles may include impurities with any starting materials, remaining particles of starting materials, carbon, or any combination thereof.

[0136] In another exemplary synthesis, the ammonium-containing ternary halide can be used directly to form the halide material. Referring to the exemplary synthesis reaction described above, after separately forming (NH4)3YCl6 and (NH4)3YBr6, the reaction mixture of (NH4)3YCl6 and LiCl can be combined with the reaction mixture of (NH4)3YBr6 and LiBr in aqueous solution, and the mixture including the four reactants can be dried together to form Li3Y(Cl 1-u Br u ) 6. The sublimation of ammonium halide can be carried out at 550°C.

[0137] After the sublimation of the ammonium halide, cooling can be performed to form a halide material. For example, cooling can be performed in air, dry air, or a nitrogen atmosphere. In another example, a cooling temperature such as less than 200°C, at most 100°C, at most 70°C, at most 50°C, or at most 30°C can be applied. In a particular embodiment, cooling can be performed at room temperature in a dry atmosphere. Optionally, Ar or N2 can be used to facilitate cooling.

[0138] In another embodiment, an ammonium-containing metal halide including at least two halide anions of any predetermined ratio can be formed in a single step. In a particular embodiment, the ternary halide can be mixed in a stoichiometric or non-stoichiometric ratio and melted in the presence of an ammonium halide salt. Ammonium halide can help protect the reaction from moisture. In one example, each ternary halide can include two metal cations and a halide anion, wherein the halide anion can be different between the ternary halides. In certain examples, the ternary halide can include two halide anions. The metal cations can be the same or different between the ternary halides. An exemplary heating temperature can be as high as 600°C to help melt the material and promote the reaction in the solid state. The heating temperature can further help ammonium escape from the halide material. The heating can be carried out in a neutral atmosphere of nitrogen or argon. Cooling can be performed to solidify the halide material.

[0139] An exemplary synthesis process is shown below. The reaction shown can allow the formation of an ammonium-containing metal halide in one step from starting materials including Li3YCl6, Li3YBr6, and NH4Br. One skilled in the art will appreciate that various ratios of starting materials can be used to form a halide material having a predetermined ratio between halide anions.

[0140] Li3YCl6+Li3YBr6+6*NH4Br→2*(NH4)3Li3YCl3Br6

[0141] The ammonium halide can be sublimed at a heating temperature of 250° C. to 650° C. In some cases, a dopant material (such as a Me compound) can be added to the melt to promote substitution of one or more metal elements of the halide material. The reaction can be carried out in a crucible made of quartz, alumina, silica-alumina, BN, glassy carbon or graphite. Controlled cooling can be applied to the melt to solidify the halide material.

[0142] In certain embodiments, the cooling rate can be controlled to promote a specific crystal growth rate, thereby allowing the growth of single crystals with macroscopic dimensions (such as single crystal blocks up to 10 cm). For example, cooling can be promoted by an external thermal field at a cooling rate of 10°C / hour to 50°C / hour. The crystal growth rate can be at least 0.2 mm / hour, at least 0.3 mm / hour, or at least 0.5 mm / hour. Additionally or alternatively, the growth rate can be at most 10 mm / hour, such as at most 8 mm / hour, at most 6 mm / hour, at most 5 mm / hour, at most 3 mm / hour, or at most 1 mm / hour.

[0143] In another specific embodiment, the crystal growth rate can be relatively high, such as at least 8 mm / hour, at least 10 mm / hour, at least 15 mm / hour, or at least 20 mm / hour, to promote polycrystalline crystal growth. Additionally or alternatively, the growth rate can be at most 80 mm / hour, at most 70 mm / hour, at most 60 mm / hour, at most 50 mm / hour, or at most 40 mm / hour.

[0144] In certain embodiments, solidification may be performed by applying a thermal gradient in the molten zone to promote the growth of crystals having a particular crystallographic orientation. For example, a crucible having an aspect ratio of length to diameter greater than 5 may be used to promote solidification of the block under a thermal gradient. This process may be particularly useful for anisotropic crystals. In certain cases, a strong thermal gradient may be applied, such as 10°C / cm or more.

[0145] In another embodiment, for crystals with anisotropic magnetic permeability or dielectric constant, oriented crystal growth can be performed using a strong permanent magnetic field, solidification under a strong electric field, or any combination thereof.

[0146] In another specific embodiment, crystallization of pellets or particles elongated in the crystallographic direction with higher ionic conductivity can be performed. For example, single crystal particles can be arranged to form a ceramic halide material with a specific crystallographic orientation. In other examples, casting, compaction, pressing, heating, molding, or any combination thereof can be used to promote the formation of oriented polycrystalline halide materials. In certain cases, single crystal pellets with a preferred crystallographic orientation can be used to form oriented ceramic halide materials. Optionally, an X-ray goniometer can be used to identify the orientation of the crystal. In other cases, using a supporting seed layer with a lattice parameter close to the oriented ceramic material and solidifying in a flux medium can help maintain an oriented polycrystalline structure.

[0147] The single crystal halide material formed can be a small block on the order of a few millimeters, or a dense block, or a larger ingot with a size of up to tens of centimeters. In an exemplary application, the single crystal can be ground to form a fine powder of single crystal particles. In another example, the single crystal ingot or block can be sliced ​​into thin slices. For example, the thin slice can have a thickness of 5 microns to 500 microns. Specifically, the single crystal can be sliced ​​so that the crystallographic direction with higher conductivity can be in the thickness direction of the thin slice. For example, a single crystal having a thickness of <hkl>(or <hklm>) has a higher ionic conductivity than a different crystalline orientation of the halide material that can be oriented, and can be sliced ​​so that the thickness of the slice is between <hkl>(or <hklm>)'s crystal orientation.

[0148] In some cases, when inconsistent melting occurs, the resulting parasitic phase can be removed from the solidified ingot, such as by grinding off the top portion containing the parasitic phase. When present, the parasitic phase can be up to 10% by volume of the crystal. Adding excess dopant material to the melt can help reduce the formation of parasitic phases and promote the formation of stoichiometric single-phase crystals under autogenous melting conditions (e.g., with excess LiX or NaX).

[0149] Forming the halide material using crystal growth can help further reduce one or more unreacted simple halide phases, including the metal elements Li, RE, Me, or Me. This process can promote the formation of a halide material that is substantially free of simple metal halide phases.

[0150] In another embodiment, the ammonium halide can be mixed and co-melted to form a crystalline halide material. For example, the ammonium halide can be formed separately as described in the embodiments herein, and the reaction mixtures including the ammonium halide can be combined, dried, and co-melted. In a specific example, referring to the exemplary synthesis reaction described above, after separately forming (NH4)3YCl6 and (NH4)3YBr6, the reaction mixture of (NH4)3YCl6 and LiCl can be combined with the reaction mixture of (NH4)3YBr6 and LiBr in an aqueous solution, and in a solid state reaction, at a heating temperature of up to 600°C, the mixture including the four reactants can be heated to dryness and melted together to form the halide material Li3Y(Cl 1-u Br u )6. Sublimation of the ammonium halide may occur at heated temperatures. In each case, the ammonium halide phase may be removed by decomposition at higher temperatures (such as up to 800° C.). Curing may be performed as described in the embodiments herein.

[0151] The removal of ammonium halide can be monitored by collecting and weighing the ammonium halide that escapes from the halide material. The ammonium halide can be removed completely, or in some cases, the ammonium halide phase of a specific amount can be retained in the halide material. For example, heating can be carried out at a temperature within the range of 350 ℃ to 800 ℃ for at least 15 minutes to 24 hours at most, to allow the ammonium halide to partially or completely sublime and / or decompose. The sublimation or decomposition of ammonium halide can help remove undesirable reaction products, such as water, CO , ammonia and halogen, such as by evaporation.

[0152] In one embodiment, a halide material substantially free of an ammonium halide phase can be formed. In at least one embodiment, the halide material can include a specific content of residual ammonium halide of at least 2 ppm relative to the total weight of the halide material, such as at least 10 ppm, at least 100 ppm, at least 300 ppm, at least 500 ppm, at least 0.2 wt %, at least 0.5 wt % or at least 1 wt % relative to the total weight of the halide material. Alternatively or additionally, the halide material includes up to 5 wt %, such as up to 3 wt % ammonium halide relative to the weight of the halide material. It should be noted that including up to 5 wt % ammonium halide phase in the halide material can help improve the ionic conductivity of the halide material.

[0153] After cooling and / or solidification, as shown at block 304 , a halide material may be formed.

[0154] The corresponding halide materials formed by conventional synthesis methods (such as solid-state reactions based on ball milling) typically include higher levels of impurities and, when used to grow crystals following processes such as Bridgman-Stockbarger, gradient solidification, Czochralski, or Bagdasarov (Horizontal Bridgman), may melt inconsistently and the formed crystals may have higher levels of impurities and parasitic phases.

[0155] Direct crystal growth using simple compounds as starting materials from the melt can also produce higher levels of impurities and parasitic phases. Typical impurities and parasitic phases may include one or more simple metal halides, such as LiX and Me k+ X k , wherein X is a halogen. It is noteworthy that the methods described in the embodiments herein can promote the formation of halide materials with improved purity compared to corresponding conventional halide materials. It is further noteworthy that higher purity can promote improved ionic conductivity of the halide material. In certain embodiments, the halide material consists of a single phase.

[0156] In another aspect, the halide material may include an impurity containing a metal nitride including Me x N k (such as YN), M x N (such as LiN3), or any combination thereof. In one example, the metal nitride Me x N k The content of can be up to 0.3 wt % relative to the weight of the halide material, such as up to 0.1 wt %, up to 500 ppm, up to 300 ppm, up to 100 ppm, up to 50 ppm, up to 40 ppm, up to 30 ppm, up to 20 ppm or up to 10 ppm relative to the weight of the halide material. In another embodiment, the metal nitride Me x N k The content of can be at least 0.2 ppm relative to the weight of the halide material, such as at least 0.5 ppm, at least 1 ppm, or at least 2 ppm relative to the weight of the halide material. In another aspect, the metal nitride Me x N k The content can be within a range including any of the minimum or maximum values ​​noted herein.

[0157] In one example, the metal nitride M x The content of N can be at most 0.3 wt % relative to the weight of the halide material, such as at most 0.1 wt %, at most 500 ppm, at most 300 ppm, at most 100 ppm, at most 50 ppm, at most 40 ppm, at most 30 ppm, at most 20 ppm or at most 10 ppm relative to the weight of the halide material. x The content of N can be at least 0.2 ppm relative to the weight of the halide material, such as at least 0.5 ppm, at least 1 ppm, or at least 2 ppm relative to the weight of the halide material. x The N content can be within a range including any of the minimum or maximum values ​​noted herein.

[0158] In one example, the total content of metal nitrides can be at most 0.3 wt % relative to the weight of the halide material, such as at most 0.1 wt %, at most 500 ppm, at most 300 ppm, at most 100 ppm, at most 50 ppm, at most 40 ppm, at most 30 ppm, at most 20 ppm, or at most 10 ppm relative to the weight of the halide material. In another case, the total content of metal nitrides can be at least 0.2 ppm relative to the weight of the halide material, such as at least 0.5 ppm, at least 1 ppm, or at least 2 ppm relative to the weight of the halide material. In another aspect, the total content of metal nitrides can be within a range including any of the minimum or maximum values ​​described herein.

[0159] In the present disclosure, metal nitrides (such as alkali metal nitrides and Me x N k ) content can be detected using the following method. The ion conductive material can be dissolved in water, because the complex metal halide can be hygroscopic. The metal nitride is not hygroscopic and can be collected and analyzed after filtering the aqueous solution. X-ray diffraction analysis can be used to detect metal nitrides with a content above 0.2 wt%. For contents below 0.2 wt%, LECO can be used.

[0160] In one embodiment, the halide material may include a crystalline structure including stacking faults. Stacking faults represent defects in the crystalline structure caused by a shift in the position of occupied or vacant atoms, which creates a disorder of the crystalline planes in the crystalline structure.

[0161] In a particular embodiment, the halide material may include a crystalline structure including a specific amount of stacking faults that may promote improved properties of the halide material. Stacking faults may result in changes in the X-ray powder diffraction pattern, particularly resulting in an inhomogeneous broadening of only certain X-ray diffraction peaks. In the present disclosure, stacking faults may be determined by using X-ray powder diffraction analysis and DIFFaX simulation of halide-based materials and by using software (such as Bruker Germany's TOPAS4.2 or FullProf (version 7.30, published in March 2020) or another version or software equivalent to TOPAS 4.2 or FullProf version 7.30) Rietveld refinement, following the stacking fault quantitative method described by Boulineau et al., Solid State Ionics, Vol. 180 (2010), pp. 1652-1659, which is incorporated herein by reference in its entirety. In short, the quantitative method may include fitting the simulation to the X-ray diffraction pattern of a powder of a halide-based material. The simulation can define the major blocks of the crystalline structure. These major blocks can be composed of plates and spaces between the plates. The major blocks can then be stacked according to one of two or more possible stacking vectors. The unique occurrence of only one of the stacking vectors results in perfect stacking, i.e., 0% stacking faults. Alternation of the stacking vectors in the stacking directions of the crystalline structure produces stacking faults. Fitting the simulation to the X-ray diffraction pattern of the halide-based material can include changing one or more parameters of the crystalline structure (also known as "parameter refinement") and implementing a least squares difference minimization algorithm, and stacking faults can be identified and quantified.

[0162] In other embodiments, the halide material may include a crystalline structure having at least 20% stacking faults, such as at least 25%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80% or at least 90% stacking faults. In a specific embodiment, the stacking of atomic layers may be completely disordered. For example, the crystalline structure may include 100% stacking faults. In another embodiment, the stacking fault may be up to 99%, such as up to 95%, up to 92%, up to 90%, up to 85%, up to 80%, up to 75% or up to 70%. In addition, the crystalline structure may include stacking faults within a range including any of the minimum percentages and maximum percentages described herein. In a specific example, the solid electrolyte material may include a halide material having a crystalline structure including at least 50% stacking faults. In another specific example, the solid electrolyte material may include a halide material having greater than 50% and up to 100% stacking faults.

[0163] In one embodiment, the halide material can be in the form of a powder, such as particles comprising a complex metal halide. In one aspect, the powder can have an average particle size (D50) of at least 0.1 micron, such as at least 0.3 micron, at least 0.5 micron, or at least 1 micron. In another aspect, the average particle size can be at most 1 mm, at most 800 microns, at most 500 microns, at most 200 microns, at most 100 microns, at most 50 microns, at most 10 microns, at most 5 microns, or at most 1 micron. In certain cases, the powder may include particles having an average particle size within a range including any of the minimum or maximum values ​​described herein. In another aspect, the powder may include aggregated or agglomerated particles.

[0164] In another aspect, the particles can have a specific shape that can promote improved formation and performance of the electrolyte and / or electrode. For example, the particles can be spherical or elongated. In another example, the particles can have the shape of a rod, a flake, or a needle. The shape of the particles can be selected based on the 2D or 1D anisotropy of the ionic conductivity of the halide material.

[0165] In another aspect, the powder may include particles having a specific average aspect ratio of length: width to promote the formation of electrolytes and / or electrodes with improved ionic conductivity. In one example, the average aspect ratio may be at least 1, such as at least 1.2, at least 1.5, at least 2, at least 2.3, at least 2.5, at least 2.8, or at least 3. In another example, the average aspect ratio may be at most 30, at most 25, at most 22, at most 20, at most 15, at most 12, at most 10, at most 8, at most 5, or at most 4. In addition, the particles may have an average aspect ratio within a range including any of the minimum and maximum values ​​described herein.

[0166] In another embodiment, the halide material can be single crystal. The halide material can be in the form of a single crystal wafer, a single crystal film, a single crystal block, a single crystal ingot or another form of single crystal, or any combination thereof. In another embodiment, the halide material can be a ceramic material. The ceramic material can include ceramic particles, single crystal particles, or any combination thereof.

[0167] In another embodiment, the halide material can be oriented to have a crystallographic orientation that has a higher ionic conductivity. For example, the halide material can be an oriented single crystal or an oriented ceramic.

[0168] In one embodiment, the solid electrolyte may include any form of halide material described in the embodiments herein. In a particular application, the solid electrolyte material may be composed of a halide material. In at least one application, the solid electrolyte material may include another material other than the halide material. For example, another material may include a solid electrolyte material, an electronically conductive material, an additive, an active electrode material, or a combination thereof that is different from the halide material.

[0169] In one embodiment, the composite ion conducting layer may include a solid electrolyte material and an organic material. The organic material may include a binder material, a polymer electrolyte material, or a combination thereof. In another example, the composite ion conducting layer may include a plasticizer, a solvent, or a combination thereof. Exemplary organic materials may include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluororubber, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, natural butyl rubber (NBR), paraffin, polypropylene carbonate, polyisobutylene, polyvinyl pyrrolidone, polymethyl methacrylate, poly(propylene oxide), polyvinyl chloride, poly(vinylidene fluoride), poly(acrylonitrile), poly(dimethylsiloxane), poly[bis(methoxyethoxyethanol salt)-phosphazene], polyethylene carbonate, polypropylene glycol, polycaprolactone, poly(trimethylene carbonate), hydrogenated nitrile rubber, poly(ethylene vinyl acetate), high density polyethylene, low density polyethylene, polyurethane, or any combination thereof. In another example, the composite ion conducting layer may include a lithium salt. Exemplary lithium salts may include LiSbF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, LiAsF6, LiClO4, LiPF6, LiBF4, LiCF3SO3, or any combination thereof.

[0170] In one embodiment, the cathode electrolyte material may include a solid electrolyte material, including a halide material. The cathode electrolyte material may also include a cathode active material. Examples of cathode active materials may include, but are not limited to, lithium-containing transition metal oxides such as Li(NiCoAl)O2 and LiCoO2, transition metal fluorides, polyanions and fluorinated polyanion materials, and transition metal sulfides, transition metal fluorides, transition metal oxysulfides, transition metal oxynitrides, etc., or any combination thereof. In a specific example, the cathode electrolyte material may include particles of the cathode active material, at least some of which may be coated with a solid electrolyte material. In a more specific example, at least a portion of the surface of each particle of the cathode active material may be coated with a solid electrolyte material. In another more specific example, the surface of most or all of the cathode active material particles may be coated with a solid electrolyte material.

[0171] In another embodiment, the anolyte material may include a solid electrolyte material, including a halide material. The anolyte may also include an active material. Exemplary anode active materials may include carbon materials (such as artificial graphite, graphite carbon fiber, resin-baked carbon, pyrolysis vapor-grown carbon, coke, mesophase carbon microbeads (MCMB), furfuryl alcohol resin-baked carbon, polyphenylene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, non-graphitizable carbon, etc.), metal materials (including lithium metal, lithium alloys, etc.), oxides, nitrides, tin compounds, silicon compounds, or any combination thereof. In some cases, the anolyte material may include an electronically conductive additive. Examples of electronically conductive additives may include carbon fibers, carbon powder, stainless steel fibers, nickel-plated graphite, etc., or any combination thereof. In a specific example, the anolyte material may include particles of an anode active material, wherein at least some of the particles may be coated with a solid electrolyte material. In a more specific example, at least a portion of the surface of each particle of the active material may be coated with a solid electrolyte material. In another more specific example, the surface of most or all of the active material particles may be coated with a solid electrolyte material.

[0172] In further embodiments, the solid electrolyte material may be formed into a layer, such as a catholyte layer, an anolyte layer, or an electrolyte layer, or a combination thereof. In further embodiments, the layer may be a component of an electrochemical device.

[0173] In another embodiment, a structure (such as a portion of an electrochemical device) may include a solid electrolyte layer, an electrode layer, and an intermediate layer disposed between the solid electrolyte layer and the electrode layer, wherein at least one of the intermediate layer, the electrolyte layer, and the electrode layer may include a solid electrolyte material. In one embodiment, the electrochemical device may include a solid-state lithium battery. See Figure 4 , showing a portion of a cross-section of an exemplary solid-state battery pack 400, the solid-state battery pack including an electrolyte layer 402 and an intermediate layer 406 disposed between an electrode layer 404 and the electrolyte layer 402. In one example, the intermediate layer 406 may include a solid electrolyte material. In a particular example, the electrode layer 404 may include an anode layer, and the intermediate layer 406 may include an anode electrolyte layer adjacent to the anode layer. In another particular example, the electrode layer 404 may include a cathode layer, and the intermediate layer 406 may include a cathode electrolyte layer adjacent to the cathode layer.

[0174] The intermediate layer 406 may include a thickness of up to 500 microns, such as up to 400 microns, up to 300 microns, up to 200 microns, up to 100 microns, or up to 50 microns. Additionally or alternatively, the intermediate layer may have a thickness of at least 5 microns, at least 8 microns, at least 10 microns, at least 12 microns, or at least 20 microns. Further, in a particular example, the thickness of the intermediate layer may be in a range including any of the minimum and maximum values described herein.

[0175] Fig. 7A Including an illustration of a portion of an electrochemical device 700 according to one embodiment, the electrochemical device including a solid electrolyte layer 704 that includes the solid electrolyte material of the embodiments herein that covers an electrode layer. Specifically, the solid electrolyte material may include a halide material that includes at least one of Cl and F and optionally another halogen element, such as Br, I, or both. The electrode layer may include a cathode layer that includes a cathode active material, where at least a portion of the cathode active material may be in contact with the solid electrolyte material. As shown, the electrode layer 702 and the electrolyte layer 704 are in contact with each other. In a particular embodiment, when a voltage is applied to the electrochemical device 700, the solid electrolyte layer 704 may be capable of forming a concentration gradient of one or more halogen anions. For example, the solid electrolyte layer 704 may include Li3Y(Br u Cl 1-u )6, where 0 < u < 1, and forms a concentration gradient of Br−, Cl - concentration gradient or both. More specifically, at this voltage, the solid electrolyte layer 704 may include a chlorine-deficient region near the electrode layer 702, where the chlorine-deficient region may include a lower concentration of chlorine compared to a region of the solid electrolyte layer 704 that is farther from the electrode layer 702. The concentration of the halogen anion may be a concentration in atomic % or mole % relative to the total amount of anions.

[0176] See Figure 7B , the electrochemical device 750 may include a solid electrolyte layer 704 and an electrode layer 702. In a particular example, the electrode layer 702 may be a cathode layer. As shown, the electrochemical device 750 may include an intermediate layer 703 between the solid electrolyte layer 704 and the electrode layer 702, wherein at least a portion of the intermediate layer 703 may be in contact with at least a portion of the cathode active material. As shown, the intermediate layer 703 may be in contact with the solid electrolyte layer 704 and the electrode layer 702. In a particular example, the intermediate layer 703 may include a lithium-metal halide material different from the solid electrolyte material, wherein the lithium-metal halide material may include at least one halogen anion that is the same as the halogen anion of the solid electrolyte material. For example, the intermediate layer may include a lithium-metal halide represented by Li 3-x- f M f RE 1-y Me k y (Cl 1-p F p ) 6-x+y*(k-3) , where -1 <= x <= 1, 0 <= y <= 1, 0 <= p <= 1 / 3, and 0 <= f <= 0.3. In a particular embodiment, the solid electrolyte layer may include an electrolyte material comprising a halide material represented by Li 3-x-f M f RE 1-y Me k y (Cl 1-p F p ) 6-x+y*(k-3) , where 0 < p <= 1 / 3, and the intermediate layer may include a lithium-metal halide represented by Li 1-x-f M f RE 1-y Me k y F 4-x+y*(k-3) , -0.3 <= x <= 0.3, 0 <= y <= 1, and 0 <= f <= 0.3. In a more particular example, the solid electrolyte material may include Li3Y(Br u Cl 1-u )6, where 0 < u < 1, and the intermediate layer may include a lithium-metal halide represented by Li 3(1-z) Y (1+z) Cl6, where 0 <= z < 0.3. The solid electrolyte material may help stabilize the intermediate layer over time under oxidative conditions. For example, the solid electrolyte material may help maintain one or more halogen anions of the intermediate layer over time to reduce decomposition of the intermediate layer, which may be due to consumption of the halogen anions under oxidative conditions. The solid electrolyte layer 704 may further help maintain the Li + Ionic current, cationic current, or both. Figure 7B As shown, under voltage conditions such as solid-state battery charging conditions, Li + Ions can flow in direction 751.

[0177] In other embodiments, the interlayer 703 may have improved oxidative stability when placed in contact with the cathode layer. Specifically, the interlayer may exhibit reduced decomposition compared to an interlayer comprising Li3YBr6. In certain embodiments, the interlayer may be capable of forming Cl under oxidative conditions. - This allows the interlayer to act as a self-passivation layer under battery operation. More specifically, under oxidizing conditions, the Cl - Compared with the concentration, a higher concentration of Cl can be formed near the cathode layer. - . Even more specifically, Cl - The concentration of may decrease in a direction from the surface in contact with the cathode layer to the opposite surface of the intermediate layer.

[0178] In a particular embodiment, the intermediate layer 703 may be a passivation layer with a specific thickness, which can promote the improved performance or formation of an electrochemical device. For example, the intermediate layer may include a thickness of at most 1 micron, at most 800nm, at most 600nm, at most 400nm, at most 300nm, at most 200nm, at most 100nm, at most 80nm, at most 60nm, at most 50nm, at most 40nm, at most 20nm, at most 10nm or at most 8nm. In another example, the intermediate layer may include a thickness of at least 1nm, at least 2nm, at least 3nm, at least 4nm, at least 5nm, at least 10nm, at least 20nm or at least 50nm. In addition, the intermediate layer may include a thickness in the range of any one of the minimum and maximum values ​​described herein. In a particular case, the intermediate layer may have a thickness in the range of at least 2nm and at most 5nm.

[0179] In one embodiment, the intermediate layer can be formed in situ from the solid electrolyte material. In one embodiment, the intermediate layer can be formed at the interface between the solid electrolyte material and the cathode active material. For example, the intermediate layer can be formed at the interface between particles of the cathode active material and particles of the solid electrolyte material, wherein the particles of the cathode active material can be coated with one or more of the particles of the solid electrolyte material. In another example, see Fig. 7A , an intermediate layer may be formed by a solid electrolyte material at the interface between the solid electrolyte layer 704 and the electrode layer 702 .

[0180] In other embodiments, forming the intermediate layer may include applying a voltage to an electrochemical device, such as 700, comprising an interface between a solid electrolyte material and a cathode active material. In one example, the voltage may include a voltage of at least 3.0 V, at least 3.6 V, at least 4.0 V, at least 4.5 V, or at least 5.0 V. In another example, the voltage may be at most 5.1 V.

[0181] In one embodiment, forming the intermediate layer may include partially decomposing a solid electrolyte material including at least one of Cl and F. In an exemplary embodiment, the solid electrolyte material may include Li3Y(Br u Cl 1-u )6 represents a halide material. Under voltage, Li3Y(Br u Cl 1-u )6 can undergo an electrochemical reaction that can cause Li3Y(Br u Cl 1-u )6 partially decomposes and forms Li3YBr at the interface 6u and Li3YCl (1-u)6 .

[0182] Li3YCl (1-u)6 Can be formed into a thin intermediate layer in contact with the cathode active material. Li3YBr 6u can be reorganized and replaced by the solid electrolyte material Li3Y(Br u Cl 1-u )6Absorption.

[0183] See also Fig. 7A and Figure 7B , partial decomposition of the solid electrolyte layer 704 under voltage may result in the formation of the intermediate layer 703. In addition, a Cl- and / or F- deficient region may be formed within the solid electrolyte layer 704. As shown, a region 756 close to the cathode active material included in the electrode layer 702 may include a lower concentration of Cl- and / or F- than a region 758 far from the cathode active material.

[0184] Known techniques can be used to form an electrolyte, a composite ion conducting layer, an anode, a cathode, an anolyte, a catholyte, an intermediate layer, or another component of an electrochemical device having a solid electrolyte material of an embodiment of the present invention. Such techniques include, but are not limited to, casting, molding, deposition, printing, pressing, heating, etc., or any combination thereof. In order to form a multilayer structure, layers (such as electrolytes, electrodes, anolytes, and catholytes) can be formed separately and then laminated to form a multilayer structure. Alternatively, a stack of green sheets can be formed, followed by further processing, such as pressing, heating, drying, or any combination thereof, to form the final multilayer structure.

[0185] In certain embodiments, a single crystal block or ingot may be processed together with the cathode or anode active material, such as by mechanical pressing or by heat activated coextrusion, to ensure intimate contact of the electrode with the electrolyte.

[0186] In another specific embodiment, single crystal blocks and ingots of halide materials can be grown directly around particles of anode and / or cathode active materials to form an anolyte or catholyte layer. In one aspect, the anolyte or catholyte layer can include single crystal halide materials, including inclusions containing anode or cathode active materials. In another aspect, the catholyte or anolyte layer can include anode or cathode active materials densely packed within a single crystal ingot or block.

[0187] Many different aspects and embodiments are possible. Some of those aspects and embodiments are described herein. After reading this specification, the technical staff will understand that those aspects and embodiments are only exemplary and do not limit the scope of the present invention. Embodiment can be according to any one or more embodiments in the embodiments listed below.

[0188] Implementation

[0189] Embodiment 1. A solid electrolyte material comprising a halide material including at least two halide anions selected from the group consisting of F, Cl, Br and I and composed of Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p- q Br u F p I q ) 6-x+y*(k-3) Representation, wherein: -1<=x<=1; 0<=y<=1; 0<=u<1; 0<=p<=1 / 3; 0<=q<=1 / 6; 0<(u+p+q)<1; 0<=f<=0.3; M is at least one alkali metal element other than Li; RE is a rare earth element; k is the valence of Me; and Me is at least one element from the group consisting of Group IIIB elements, Group IVB elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, Sn, Pb, Bi, Sb, Mg, Ca, Ga and Ge, wherein Me is different from RE; and wherein the halide material includes, relative to the total weight of the halide material: a total content of one or more binary halide phases of not more than 10 weight %; a total content of one or more oxyhalide phases of not more than 7 weight %; and a total content of one or more ternary halide phases of not more than 7 weight %.

[0190] Embodiment 2. The solid electrolyte material of Embodiment 1, wherein the halide material comprises an X-ray diffraction pattern measured with Cu K-alpha radiation comprising the absence of a peak between 5° and 13° 2θ.

[0191] Embodiment 3. A solid electrolyte material according to Embodiment 1 or 2, wherein the halide material comprises no more than 9 weight % of a binary halide phase, no more than 8 weight %, no more than 7 weight %, no more than 6 weight %, no more than 5 weight %, no more than 4 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of a binary halide phase relative to the total weight of the halide material.

[0192] Embodiment 4. A solid electrolyte material according to any one of Embodiments 1 to 3, wherein the binary phase includes a lithium halide phase, wherein the halide material includes no more than 7 weight % of the lithium halide phase, no more than 6 weight %, no more than 5 weight %, no more than 4 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of the lithium halide phase relative to the total weight of the halide material.

[0193] Embodiment 5. A solid electrolyte material according to any one of Embodiments 1 to 4, wherein the binary phase includes a rare earth halide phase, wherein the halide material includes no more than 10 weight % of the rare earth halide phase, no more than 7 weight %, no more than 5 weight %, no more than 4 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of the rare earth halide phase relative to the total weight of the halide material.

[0194] Embodiment 6. A solid electrolyte material according to any one of Embodiments 1 to 5, wherein the halide material includes no more than 6 weight % of a ternary halide phase, no more than 5 weight %, no more than 4 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of a ternary halide phase relative to the total weight of the halide material.

[0195] Embodiment 7. A solid electrolyte material according to any one of Embodiments 1 to 6, wherein the ternary halide phase includes a ternary phase comprising two anions, wherein the halide material includes no more than 7 weight % of the ternary halide phase comprising two anions, no more than 4 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of the ternary halide phase comprising two anions relative to the total weight of the halide material.

[0196] Embodiment 8. A solid electrolyte material according to any one of Embodiments 1 to 6, wherein the ternary phase includes a lithium-rare earth halide phase, wherein the halide material includes no more than 7 weight % of the lithium-rare earth halide phase, no more than 5 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of the lithium-rare earth halide phase relative to the total weight of the halide material.

[0197] Embodiment 9. A solid electrolyte material according to any one of Embodiments 1 to 8, wherein the halide material comprises no more than 6 weight % of an oxyhalide phase, no more than 5 weight %, no more than 4 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of an oxyhalide phase relative to the total weight of the halide material.

[0198] Embodiment 10. A solid electrolyte material according to any one of Embodiments 1 to 9, wherein the oxyhalide phase includes a rare earth oxyhalide phase, wherein the halide material includes no more than 7 weight % of the rare earth oxyhalide phase, no more than 5 weight %, no more than 4 weight %, no more than 3 weight %, no more than 2 weight %, no more than 1 weight % or no more than 0.5 weight % of the rare earth oxyhalide phase relative to the total weight of the halide material.

[0199] Embodiment 11. The solid electrolyte material according to any one of Embodiments 1 to 10, wherein the halide material does not contain at least one phase selected from the group consisting of a binary halide phase, a ternary halide phase, and an oxyhalide phase.

[0200] Embodiment 12. The solid electrolyte material according to any one of Embodiments 1 to 11, wherein the halide material does not contain a binary halide phase, a ternary halide phase, and an oxyhalide phase.

[0201] Embodiment 13. An electrolyte material comprising a halide material including at least two halide anions selected from the group consisting of F, Cl, Br, and I in a single phase, wherein the halide material is composed of Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p-q Br u F p I q ) 6-x+y*(k-3) Represents, wherein: -1<=x<=1; 0<=y<=1; 0<=u<1; 0<=p<=1 / 3; 0<=q<=1 / 6; 0<(u+p+q)<1; 0<=f<=0.3; M is at least one alkali metal element other than Li; RE is a rare earth element; k is the valence of Me; and Me is at least one element selected from the group consisting of Group IIIB elements, Group IVB elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, Sn, Pb, Bi, Sb, Mg, Ca, Ga and Ge, wherein Me is different from RE.

[0202] Embodiment 14. A solid electrolyte material according to any one of Embodiments 1 to 13, wherein the halide material comprises a crystalline structure of a monoclinic, trigonal, hexagonal or orthorhombic crystal system.

[0203] Embodiment 15. A solid electrolyte material according to Embodiment 14, wherein the halide material comprises a crystalline structure represented by a rhombohedral space group.

[0204] Embodiment 16. A solid electrolyte material according to Embodiment 14 or 15, wherein the crystalline structure includes a unit cell that is smaller than a unit cell of Li3YBr6.

[0205] Embodiment 17. A solid electrolyte material according to any one of Embodiments 1 to 16, wherein the peaks of the powder diffraction pattern of the halide material are shifted to higher angles compared to the corresponding peaks of the powder diffraction pattern of Li3YBr6.

[0206] Embodiment 18. The solid electrolyte material according to any one of Embodiments 1 to 17, wherein the halide material is Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p Br u F p ) 6-x+y*(k-3) express.

[0207] Embodiment 19. A solid electrolyte material according to any one of Embodiments 1 to 18, wherein the halide material is Li 3-x-f M f RE 1-y Me k y (Cl 1-u Br u ) 6-x+y*(k-3) express.

[0208] Embodiment 20. The solid electrolyte material according to any one of Embodiments 1 to 18, wherein the halide material is Li 3-x-f M f RE 1-y Me k y (Cl 1-p F p ) 6-x+y*(k-3) Indicates that 0<=p<2.

[0209] Embodiment 21. A solid electrolyte material according to any one of Embodiments 1 to 20, wherein RE comprises Y, Ce, Gd, Er, La or Yb.

[0210] Embodiment 22. A solid electrolyte material according to any one of Embodiments 1 to 21, wherein Me includes Y, Ce, Gd, Er, Sm, Eu, Pr, Tb, Al, Zr, La, Yb, Mg, Zn, Sn, Mg, Ca or any combination thereof.

[0211] Embodiment 23. A solid electrolyte material according to any one of Embodiments 1 to 22, wherein RE is composed of Y.

[0212] Embodiment 24. The solid electrolyte material according to any one of Embodiments 1 to 23, wherein Me is at least one element selected from the group consisting of Gd, Yb, Zr, Zn, Mg, Al and Ca.

[0213] Embodiment 25. A solid electrolyte material according to any one of Embodiments 1 to 24, wherein M comprises Na or K, wherein M consists of Na or K.

[0214] Embodiment 26. A solid electrolyte material according to any one of Embodiments 1 to 19 and 21 to 25, wherein u>=0.1, u>=0.12, u>=0.15, u>=0.17, u>=0.2, u>=0.23, u>=0.25, u>=0.27, u>=0.29, u>=0.32 or u>=0.34.

[0215] Embodiment 27. A solid electrolyte material according to any one of embodiments 1 to 19 and 21 to 25, wherein u<=0.85, u<=0.83, u<=0.8, u<=0.77, u<=0.75, u<=0.7, u<=0.67, u<=0.65, u<=0.62, u<=0.6, u<=0.57, u<=0.54, u<=0.52, u<=0.49, u<=0.45, u<=0.42.

[0216] Embodiment 28. A solid electrolyte material according to any one of Embodiments 1 to 20 and 22 to 25, wherein p>=0.04, p>=0.06, p>=0.08, p>=0.09, p>=0.10, p>=0.12, p>=0.14, p>=0.15, p>=0.17, p>=0.2 or p>=0.22.

[0217] Embodiment 29. A solid electrolyte material according to any one of embodiments 1 to 20, 22 to 25 and 28, wherein p<=0.33, p<=0.31, p<=0.29, p<=0.27, p<=0.25, p<=0.22, p<=0.20, p<=0.18, p<=0.16, p<=0.14 or p<=0.10.

[0218] Embodiment 30. A solid electrolyte material according to any one of Embodiments 1 to 29, wherein (1-upq)>=0.12, (1-upq)>=0.15, (1-upq)>=0.17, (1-upq)>=0.20, (1-upq)>=0.23, (1-upq)>=0.25, (1-upq)>=0.27, (1-upq)>=0.29, (1-upq)>=0.33, (1-upq)>=0.36, (1-upq)>=0.43, (1-upq)>=0.48, (1-upq)>=0.50, (1-upq)>=0.54 or (1-upq)>=0.58.

[0219] Embodiment 31. A solid electrolyte material according to any one of Embodiments 1 to 30, wherein (1-upq)<=0.97, (1-upq)<=0.92, (1-upq)<=0.87, (1-upq)<=0.83, (1-upq)<=0.80, (1-upq)<=0.77, (1-upq)<=0.75, (1-upq)<=0.70 or (1-upq)<=0.66.

[0220] Embodiment 32. A solid electrolyte material according to any one of Embodiments 1 to 19 and 21 to 31, wherein the ratio of (1-upq) / u is at least 0.03, at least 0.06, at least 0.1, at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 1.0, at least 1.2, at least 1.3, at least 1.4, at least 1.5, at least 1.6, at least 1.7, at least 1.8, at least 1.9 or at least 2.0.

[0221] Embodiment 33. A solid electrolyte material according to any one of Embodiments 1 to 19 and 21 to 32, wherein the ratio of (1-upq) / u is not greater than 15, not greater than 11, not greater than 10, not greater than 9, not greater than 8, not greater than 7, not greater than 6, not greater than 5, not greater than 4, not greater than 3, not greater than 2 or not greater than 1.4.

[0222] Embodiment 34. A solid electrolyte material according to any one of Embodiments 1 to 19 and 21 to 33, wherein the halide material is Li 3-x RE 1-y Me k y (Cl 1-u Br u ) 6-x+y*(k-3) Indicates that 0.08<=u<=0.67.

[0223] Embodiment 35. The solid electrolyte material according to Embodiment 34, wherein the halide material is Li 3-x Y(Cl 1-u Br u )6 indicates.

[0224] Embodiment 36. A solid electrolyte material according to Embodiment 34 or 35, wherein u>=0.55 or u<=0.45.

[0225] Embodiment 37. A solid electrolyte material according to any one of Embodiments 34 to 36, wherein 0.2<=u<=0.45.

[0226] Embodiment 38. A solid electrolyte material according to any one of Embodiments 34 to 37, wherein u<0.33.

[0227] Embodiment 39. A solid electrolyte material according to any one of Embodiments 1 to 38, wherein the halide material comprises an X-ray diffraction pattern measured with Cu K-alpha radiation comprising at least two peaks in the range of 13° to 15° 2θ.

[0228] Embodiment 40. A solid electrolyte material according to any one of Embodiments 1 to 39, wherein the halide material comprises an average diffraction crystallite size of at least 20 nm, at least 25 nm, at least 30 nm, at least 35 nm, or at least 40 nm.

[0229] Embodiment 41. A solid electrolyte material according to any one of Embodiments 1 to 40, wherein the halide material comprises an average diffraction crystallite size of at most 500 nm, at most 400 nm, at most 300 nm, at most 200 nm, or at most 100 nm.

[0230] Embodiment 42. A solid electrolyte material according to any one of Embodiments 1 to 41, wherein the halide material comprises greater than 2.3 g / cm 3 , at least 2.5g / cm 3 , at least 2.7g / cm 3 , at least 2.9g / cm 3 , at least 3.1g / cm 3 , at least 3.3g / cm 3 , or at least 3.5g / cm 3 density.

[0231] Embodiment 43. A solid electrolyte material according to any one of Embodiments 1 to 42, wherein the halide material comprises less than 3.8 g / cm 3 , not more than 3.5g / cm 3 , not more than 3.4g / cm 3 , not more than 3.3g / cm 3 , or not more than 3.1g / cm 3 density.

[0232] Embodiment 44. A solid electrolyte material according to any one of Embodiments 1 to 43, wherein the halide material comprises a thermodynamic electrochemical stability value greater than 3.57V, at least 3.60V, at least 3.62V, 3.65V, or at least 3.71V.

[0233] Embodiment 45. A solid electrolyte material according to any one of Embodiments 1 to 44, wherein the halide material comprises a thermodynamic electrochemical stability value of no greater than 4.30 V, no greater than 4.19 V, no greater than 4.15 V, no greater than 4.10 V, no greater than 3.85 V, no greater than 3.80 V, no greater than 3.75 V, or no greater than 3.71 V.

[0234] Embodiment 46. A solid electrolyte material according to any one of Embodiments 1 to 45, wherein the halide material has improved electrochemical stability compared to Li3YBr6.

[0235] Embodiment 47. A solid electrolyte material according to any one of Embodiments 1 to 45, wherein the halide material comprises an ionic conductivity greater than 0.15 mS / cm, at least 0.3 mS / cm, at least 0.5 mS / cm, at least 0.8 mS / cm, at least 0.9 mS / cm, at least 1.1 mS / cm, at least 1.5 mS / cm or at least 1.7 mS / cm measured at 22°C.

[0236] Embodiment 48. A solid electrolyte material according to any one of Embodiments 1 to 45, wherein the halide material has an ionic conductivity of less than 2.0 mS / cm, at most 1.9 mS / cm, at most 1.8 mS / cm, or at most 1.7 mS / cm measured at 22°C.

[0237] Embodiment 49. A cathode electrolyte material comprising the solid electrolyte material according to any one of Embodiments 1 to 48.

[0238] Embodiment 50. The catholyte material of Embodiment 49, comprising particles of cathode active material, wherein at least some of the particles are coated with a solid electrolyte material.

[0239] Embodiment 51. An anolyte material comprising the solid electrolyte material according to any one of Embodiments 1 to 48.

[0240] Embodiment 52. The anolyte material of Embodiment 51 comprising particles of anode active material, wherein at least some of the particles are coated with a solid electrolyte material.

[0241] Embodiment 53. A layer comprising a solid electrolyte material according to any one of Embodiments 1 to 48, wherein the layer comprises a cathode electrolyte layer, an anode electrolyte layer, an electrolyte layer, or a combination thereof.

[0242] Embodiment 54. A catholyte layer comprising a catholyte material according to Embodiment 49 or 50.

[0243] Embodiment 55. An anolyte layer comprising the anolyte material according to Embodiment 51 or 52.

[0244] Embodiment 56. An electrochemical device comprising: a solid electrolyte layer comprising a solid electrolyte material according to any one of Embodiments 1 to 48, wherein the halide material comprises at least one of Cl and F; an electrode layer comprising a cathode active material in contact with the solid electrolyte material, wherein the solid electrolyte layer is capable of forming a chlorine-deficient or fluorine-deficient region near the electrode layer under oxidizing conditions, wherein the chlorine-deficient or fluorine-deficient region contains a lower concentration of chlorine or fluorine, respectively, compared to a region of the solid electrolyte layer away from the electrode layer.

[0245] Embodiment 57. An electrochemical device comprising: a solid electrolyte layer comprising a solid electrolyte material according to any one of Embodiments 1 to 48, an electrode layer comprising a cathode active material, and an intermediate layer located between the solid electrode layer and the cathode active material.

[0246] Embodiment 58. The electrochemical device according to Embodiment 57, wherein the intermediate layer includes a cathode electrolyte layer adjacent to the electrode layer.

[0247] Embodiment 59. The electrochemical device according to Embodiment 57, wherein the intermediate layer includes a lithium-metal halide represented by Li 3-x-f M f RE 1- y Me k y (Cl 1-p F p ) 6-x+y*(k-3) where -1 <= x <= 1, 0 <= y <= 1, 0 <= p <= 1 / 3 and 0 <= f <= 0.3.

[0248] Embodiment 60. The electrochemical device according to Embodiment 57, wherein the solid electrolyte layer includes an electrolyte material containing a halide material represented by Li 3-x-f M f RE 1-y Me k y (Cl 1-p F p ) 6-x+y*(k-3) where 0 < p <= 1 / 3, and the intermediate layer contains a lithium-metal halide represented by Li 1-x-f M f RE 1-y Me k y F 4-x+y*(k-3) where -0.3 <= x <= 0.3, 0 <= y <= 1 and 0 <= f <= 0.3.

[0249] Embodiment 61. The electrochemical device according to Embodiment 57, wherein the solid electrolyte layer includes an electrolyte material, and the electrolyte material includes a halide material represented by Li3Y(Br u Cl 1-u )6 where 0 < u < 1, and the intermediate layer includes a lithium-metal halide represented by Li 3(1-z) Y (1+z) Cl6 where 0 <= z < 0.3.

[0250] Embodiment 62. The electrochemical device according to any one of Embodiments 57 and 59 to 61, wherein the intermediate layer has a thickness of at most 1 micron, at most 800 nm, at most 600 nm, at most 400 nm, at most 300 nm, at most 200 nm, at most 100 nm, at most 80 nm, at most 60 nm, at most 50 nm, at most 40 nm, at most 20 nm, at most 10 nm or at most 8 nm.

[0251] Embodiment 63. An electrochemical device according to any one of Embodiments 57 and 59 to 62, wherein the intermediate layer comprises a thickness of at least 1 nm, at least 2 nm, at least 3 nm, at least 4 nm, at least 5 nm, at least 10 nm, at least 20 nm or at least 50 nm.

[0252] Embodiment 64. An electrochemical device according to any one of Embodiments 57 and 59 to 63, wherein the intermediate layer is a passivation layer.

[0253] Embodiment 65. A method for forming an intermediate layer of an electrochemical device, comprising: applying a voltage to the electrochemical device, wherein the electrochemical device includes an interface between a solid electrolyte material according to any one of Embodiments 1 to 48 and a cathode active material; forming an intermediate layer in contact with the cathode active material, wherein the intermediate layer includes a lithium-metal halide material different from the solid electrolyte material, and wherein the intermediate layer is formed in situ.

[0254] Embodiment 66. A method according to Embodiment 65, wherein the lithium-metal halide material is formed by partial decomposition of a solid electrolyte material, wherein the solid electrolyte material includes a halide material, and the halide material includes at least one of Cl and F.

[0255] Embodiment 67. A method according to embodiment 65 or 66, wherein the electrochemical device includes a solid electrolyte layer comprising a solid electrolyte material, and wherein the method also includes forming a Cl-deficient or F-deficient region in the solid electrolyte layer, wherein the Cl-deficient or F-deficient region is close to the intermediate layer and contains a lower concentration of Cl- or F-, respectively, compared to a region in the solid electrolyte layer far from the intermediate layer.

[0256] Embodiment 68. The method of any one of Embodiments 65 to 67, wherein the voltage comprises a voltage of at least 3.0V, at least 3.6V, at least 4.0V, at least 4.5V, at least 5.0V.

[0257] Embodiment 69. The method according to any one of Embodiments 65 to 68, wherein the intermediate layer comprises Li 3-x- f M f RE 1-y Me k y (Cl 1-p F p ) 6-x+y*(k-3) Represented by a lithium-metal halide, wherein -1<=x<=1, 0<=y<=1, 0<=p<=1 / 3 and 0<=f<=0.3.

[0258] Embodiment 70. The method according to any one of embodiments 65 to 69, wherein the electrolyte material comprises a halide material represented by Li 3-x-f M f RE 1-y Me k y (Cl 1-p F p ) 6-x+y*(k-3) where 0 < p <= 1 / 3, and the intermediate layer comprises a lithium-metal halide represented by Li 1-x-f M f RE 1-y Me k y F 4-x+y*(k-3) where -0.3 <= x <= 0.3, 0 <= y <= 1 and 0 <= f <= 0.3.

[0259] Embodiment 71. The method according to any one of embodiments 65 to 70, wherein the electrolyte material comprises a halide material represented by Li3Y(Br u Cl 1-u )6, where 0 < u < 1, and the intermediate layer comprises a lithium-metal halide represented by Li 3(1-z) Y (1+z) Cl6, where 0 <= z < 0.3.

[0260] Embodiment 72. The method according to any one of embodiments 65 to 71, wherein the intermediate layer has a thickness of at most 1 micron, at most 800 nm, at most 600 nm, at most 400 nm, at most 300 nm, at most 200 nm, at most 100 nm, at most 80 nm, at most 60 nm, at most 50 nm, at most 40 nm, at most 20 nm, at most 10 nm or at most 8 nm.

[0261] Embodiment 73. The method according to any one of embodiments 65 to 72, wherein the intermediate layer has a thickness of at least 1 nm, at least 2 nm, at least 3 nm, at least 4 nm, at least 5 nm, at least 10 nm, at least 20 nm or at least 50 nm.

[0262] Embodiment 74. A method of forming a solid electrolyte material, comprising forming a solid solution of a halide material comprising at least two halide anions selected from the group consisting of F, Cl, Br, and I, wherein the halide material is represented by Li 3-x- f M f RE 1-y Me k y (Cl 1-u-p-q Br u F p I q ) 6-x+y*(k-3) Represents, wherein: -1<=x<=1; 0<=y<=1; 0<=u<1; 0<=p<=1 / 3; 0<=q<=1 / 6; 0<=(u+p+q)<1; 0<=f<=0.3; M is at least one alkali metal element other than Li; RE is a rare earth element; k is the valence of Me; and Me is at least one element from the group consisting of Group IIIB elements, Group IVB elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, Sn, Pb, Bi, Sb, Mg, Ca, Ga and Ge, wherein Me is different from RE.

[0263] Embodiment 75. The method of Embodiment 74 further comprises forming an ammonium-containing metal halide material.

[0264] Embodiment 76. The method according to embodiment 74 or 75, further comprising forming (NH4) z RE 1-y Me k y (Cl 1-u-p-q Br u F p I q ) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (Cl 1-u Br u ) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (Cl 1- p F p ) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (Cl) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (Br) 3+z+y*(k-3) 、(NH4) z RE 1-y Me k y (I) 3+z+y*(k-3) or a combination thereof, wherein 0.33<=z<=5.

[0265] Embodiment 77. The method according to embodiment 75 or 76, wherein the formation of the ammonium-containing metal halide is carried out in a single step with a predetermined ratio between at least two halogen elements selected from the group consisting of F, Cl, Br and I.

[0266] Embodiment 78. The method of any one of Embodiments 75 to 77, wherein forming the ammonium-containing metal halide material is carried out in a liquid medium.

[0267] Embodiment 79. The method of any one of Embodiments 75 to 78, wherein forming the ammonium-containing metal halide material is carried out at a temperature of up to 250°C.

[0268] Embodiment 80. The method of Embodiment 79, wherein the temperature is at least 20°C, at least 40°C, at least 50°C, at least 70°C, at least 90°C, at least 110°C, or at least 140°C.

[0269] Embodiment 81. The method of Embodiment 79 or 80, wherein the temperature is no greater than 200°C, no greater than 180°C, no greater than 160°C, or no greater than 140°C.

[0270] Embodiment 82. The method of any one of Embodiments 78 to 81, wherein the liquid medium comprises an acidic solution.

[0271] Embodiment 83. A method according to any one of Embodiments 78 to 82, wherein the liquid medium comprises an acid comprising hydrochloric acid, hydrobromic acid, hydrofluoric acid, hydroiodic acid, or any combination thereof.

[0272] Embodiment 84. The method of any one of Embodiments 75 to 83, further comprising partially or completely thermally decomposing the ammonium-containing metal halide material into ammonium halide and lithium-containing metal halide.

[0273] Embodiment 85. The method according to Embodiment 84 also includes completely or partially separating the ammonium halide and the lithium-containing metal halide.

[0274] Embodiment 86. A solid electrolyte material according to any one of Embodiments 1 to 48, wherein the halide material comprises a crystalline structure comprising at least 20% stacking faults, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80% or at least 90% stacking faults.

[0275] Embodiment 87. A solid electrolyte material according to any one of Embodiments 1 to 48 and 86, wherein the halide material comprises a charge-neutral metal nitride comprising Me x N k 、M x N or a combination thereof, wherein x is the valence of N and k is the valence of Me, wherein the total content of charge-neutral metal nitride is up to 0.3 wt % relative to the weight of the halide material.

[0276] Embodiment 88. A solid electrolyte material comprising Li a M a’ Me b Me' b’ X c X' c’ Represents the halide material,

[0277] Among them, halide materials have crystallographic phase transitions in the following stoichiometric ranges:

[0278] Phase transition boundary (b / (b+b')) t *0.84 t *1.16, where (b / (b+b')) t Corresponding to the crystallographic phase transition boundary on the crystallographic phase diagram at a temperature of 22°C;

[0279] (c / (c+c')) t *0.84 <c / (c+c’)<(c / (c+c’)) t *1.16, where (c / (c+c')) t corresponds to a crystallographic phase transition on a crystallographic phase diagram at a temperature of 22°C; or

[0280] (a / (a+a')) t *0.84 t *1.16, among which (a / (a+a')) t Corresponding to the crystallographic phase transition on the crystallographic phase diagram at a temperature of 22°C;

[0281] in:

[0282] Me is at least one element from the group consisting of Group IIIB elements, Group IVB elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, In, Sn, Pb, Bi, Sb, Mg, Ca, Ga, and Ge; and

[0283] Me′ is at least one element other than Me and is selected from the group consisting of Group IIIB elements, Group IVB elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, In, Sn, Pb, Bi, Sb, Mg, Ca, Ga, and Ge;

[0284] ​​Where b>=b'; c>=c'; a>=a';

[0285] X is at least one halogen other than X';

[0286] X' is at least one halogen; and

[0287] M is at least one alkali metal element other than Li; and

[0288] Wherein the total weight of the halide material relative to the halide material comprises:

[0289] A total content of one or more binary halide phases of no more than 10% by weight;

[0290] a total content of one or more oxyhalide phases of no more than 7% by weight; and

[0291] The total content of one or more ternary halide phases is no greater than 7 wt%.

[0292] Embodiment 89. A solid electrolyte material comprising Li a M a Me b Me' b’ X c X' c’ Represents the halide material,

[0293] Among them, halide materials have crystallographic phase transitions in the following stoichiometric ranges:

[0294] (b / (b+b')) t *0.84 t *1.16, where (b / (b+b')) t Corresponding to the crystallographic phase transition on the crystallographic phase diagram at a temperature of 20°C to 25°C;

[0295] (c / (c+c')) t *0.84 <c / (c+c’)<(c / (c+c’)) t *1.16, where (c / (c+c')) t corresponds to a crystallographic phase transition on a crystallographic phase diagram at a temperature of 20°C to 25°C; or

[0296] (a / (a+a')) t *0.84 t *1.16, among which (a / (a+a')) t Corresponding to the crystallographic phase transition on the crystallographic phase diagram at a temperature of 20°C to 25°C; ​​

[0297] in:

[0298] Me is at least one element from the group consisting of Group IIIB elements, Group IVB elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, In, Sn, Pb, Bi, Sb, Mg, Ca, Ga, and Ge;

[0299] Me′ is at least one element other than Me and is selected from the group consisting of Group IIIB elements, Group IVB elements, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Al, In, Sn, Pb, Bi, Sb, Mg, Ca, Ga, and Ge;

[0300] wherein b>=b'; c>=c'; a>=a'; X is at least one halogen other than X';

[0301] X' is a halogen; and

[0302] M is at least one alkali metal element other than Li; and

[0303] The anions of the halide material are in a single phase.

[0304] Embodiment 90. A solid electrolyte material according to Embodiment 88 or 89, wherein the halide material comprises an X-ray diffraction pattern measured with Cu K-alpha radiation comprising the absence of a peak between 5° and 13° 2θ.

[0305] Embodiment 91. A solid electrolyte material according to any one of Embodiments 88 to 90, wherein the halide material comprises a crystalline structure of a monoclinic, trigonal, hexagonal or orthorhombic crystal system.

[0306] Embodiment 92. A solid electrolyte material according to any one of Embodiments 88 to 91, wherein the crystallographic phase transition comprises a transition from a layered crystal structure to a non-layered crystal structure.

[0307] Embodiment 93. A solid electrolyte material according to any one of Embodiments 88 to 92, wherein the crystallographic phase transition comprises a transition from a cubic close-packed structure to a hexagonal close-packed structure.

[0308] Embodiment 94. A solid electrolyte material according to any one of Embodiments 88 to 93, wherein the crystallographic phase transition comprises a transition from a C2 / m space group or an R-3m space group to a P-3m1 or Pnma space group.

[0309] Embodiment 95. A solid electrolyte material according to any one of Embodiments 88 to 93, wherein the crystallographic phase transition comprises a transition from a non-layered crystal structure to another non-layered crystal structure or to a layered crystal structure.

[0310] Embodiment 96. A solid electrolyte material according to any one of Embodiments 88 to 91 and 95, wherein the crystallographic phase transition comprises a transition from R3c to R3m.

[0311] Embodiment 97. A solid electrolyte material according to any one of Embodiments 88 to 91 and 95 to 96, wherein the crystallographic phase transition comprises a transition from a P-3m1 or Pnma space group to a C2 / m space group or an R-3m space group.

[0312] Embodiment 98. A solid electrolyte material according to any one of Embodiments 88 to 97, wherein Me is at least one rare earth element.

[0313] Embodiment 99. A solid electrolyte material according to any one of Embodiments 88 to 98, wherein Me' is at least one element of a rare earth element, In, Zr and Fe.

[0314] Embodiment 100. A solid electrolyte material according to any one of Embodiments 88 to 99, wherein M is at least one element of Na, K and Cs.

[0315] Embodiment 101. A solid electrolyte material according to any one of Embodiments 88 to 100, wherein X is at least one element of Cl and Br.

[0316] Embodiment 102. A solid electrolyte material according to any one of Embodiments 88 to 101, wherein X' is at least one element of Br and F.

[0317] Embodiment 103. A solid electrolyte material according to any one of Embodiments 88 to 102, wherein the halide material is Li a-f M a’ RE b Me' k b’ (Cl c Br c’ ) 6-f+(k-3)*b’ represents, where:

[0318] a+a'=3;

[0319] -1≤f≤1;

[0320] c+c'=1; and

[0321] b+b'=1.

[0322] Embodiment 104. A solid electrolyte material according to any one of Embodiments 88 to 102, wherein the halide material is Li 3-f RE b Me' k b’ (Cl c Br c’ ) 6-f+(k-3)*b’ represents, where:

[0323] -1≤f≤1;

[0324] c+c'=1; and

[0325] b+b'=1.

[0326] Embodiment 105. A solid electrolyte material according to Embodiment 104, wherein b>0, b'>0 and 0.65≤c / (c+c')≤0.95.

[0327] Embodiment 106. A solid electrolyte material according to Embodiment 104 or 105, wherein RE includes Y, and Me' includes In, Yb or Zr.

[0328] Embodiment 107. The solid electrolyte material of any one of Embodiments 104 to 106, wherein Me′ is Yb, and 0.65≤c / (c+c′)≤0.89.

[0329] Embodiment 108. The solid electrolyte material of any one of Embodiments 104 to 106, wherein Me′ is In, and 0.69≤c / (c+c′)≤0.95.

[0330] Embodiment 109. A solid electrolyte material according to any one of Embodiments 104 to 106, wherein the halide material is Li3Y b Yb b’ (Cl c Br c’ )6 represents, where 0.65≤c / (c+c')≤0.89.

[0331] Embodiment 110. A solid electrolyte material according to any one of Embodiments 104 to 106 and 108, wherein the halide material is Li3Y b In b’ (Cl c Br c’ )6 represents, where 0.69≤c / (c+c')≤0.95.

[0332] Embodiment 111. The solid electrolyte material of any one of Embodiments 104 to 106, wherein Me′ is Zr, and 0.72≤c / (c+c′)≤0.98.

[0333] Embodiment 112. A solid electrolyte material according to any one of Embodiments 104 to 106, wherein the halide material is Li 3-b’ Y b Zr b’ (Cl c Br c’ )6 represents, where 0.72≤c / (c+c')≤0.98.

[0334] Embodiment 113. A solid electrolyte material according to any one of Embodiments 88 to 104, wherein the halide material is Li 3-f RE(Cl c Br c’ ) 6-f represents, where:

[0335] 0<=f<=0.3;

[0336] c+c'=1; and

[0337] 0.63≤c / (c+c')≤0.87.

[0338] Embodiment 114. A solid electrolyte material according to Embodiment 113, wherein RE includes Y.

[0339] Embodiment 115. A solid electrolyte material according to Embodiment 113 or 114, wherein RE is composed of Y, wherein 0.65≤c / (c+c')≤0.87; or 0.66≤c / (c+c')≤0.85; or 0.67≤c / (c+c')≤0.83.

[0340] Embodiment 116. A solid electrolyte material according to any one of Embodiments 88 to 104, wherein the halide material is Li 3-f RE b Me' k b’ X 6-f+(k-3)*b’ represents, where:

[0341] 0<=f<=0.3; and

[0342] b+b'=1.

[0343] Embodiment 117. The solid electrolyte material of Embodiment 116, wherein 0.67≤b / (b+b′)≤0.93.

[0344] Embodiment 118. A solid electrolyte material according to Embodiment 116 or 117, wherein RE comprises Y, Me' comprises In, and X comprises Cl.

[0345] Embodiment 119. A solid electrolyte material according to any one of Embodiments 116 to 118, wherein the halide material is Li 3-f RE b In b’ X 6-f Indicates that 0.67≤b / (b+b')≤0.93.

[0346] Embodiment 120. The solid electrolyte material according to Embodiment 118, wherein the halide material is Li3Y b In b’ X6 indicates.

[0347] Embodiment 121. A solid electrolyte material according to any one of Embodiments 116 to 117, wherein the halide material is Li 3-f RE b In b’ X 6-f express.

[0348] Embodiment 122. A solid electrolyte material according to any one of Embodiments 88 to 103, wherein the halide material is Li a M a’ REX6 said that among them:

[0349] a>a'>0;

[0350] a+a'=3; and

[0351] 0.942≤a / (a+a')≤0.958.

[0352] Embodiment 123. A solid electrolyte material according to Embodiment 122, wherein M comprises Na.

[0353] Embodiment 124. A solid electrolyte material according to Embodiment 122 or 123, wherein RE includes Y.

[0354] Embodiment 125. A solid electrolyte material according to any one of Embodiments 122 to 124, wherein X comprises Cl.

[0355] Embodiment 126. A solid electrolyte material according to any one of Embodiments 122 to 124, wherein the halide material is Li a Na a’ YCl6 indicates.

[0356] Embodiment 127. The solid electrolyte material according to any one of Embodiments 88 to 126, when the halide material therein has a crystallographic phase transition within a stoichiometric range of (c / (c + c'))t * 0.84 < c / (c + c') < (c / (c + c'))t * 1.16, where (c / (c + c'))t corresponds to the crystallographic phase transition on the crystallographic phase diagram at a temperature of 20 °C to 25 °C, and when c / (c + c') < 0.75, the halide material comprises an X-ray diffraction pattern measured with Cu K-α radiation, including at least two peaks in the range of 13° to 15° 2θ.

[0357] Example

[0358] Example 1

[0359] According to the embodiments herein, Samples 1 to 8 were synthesized by forming a solid solution of (NH4)3Li3YBr6 and (NH4)3Li3YCl6. The composition and properties of the samples are recorded in Table 1.

[0360] At room temperature (about 22 °C), under the conditions of an AC frequency of 3 MHz to 10 Hz and a peak-to-peak sinusoidal AC voltage signal of 10 mV to 50 mV, the ionic conductivity of the samples was measured using the electrochemical impedance spectroscopy method with a gold blocking electrode.

[0361] The ionic conductivity of the bulk grains is included in Table 1. The conductivity contribution from the bulk grains can be separated from the grain boundaries and electrode contacts because the bulk grain conductivity characteristics appear at the highest frequencies and are associated with the lowest value of the double-layer capacitance.

[0362] Table 1

[0363]

[0364] Example 2

[0365] The following samples were formed. Sample 9 includes a counter electrode of In / Li foil, a separator made of a solid solution of Li3YBr2Cl4 formed in the same manner as described in Example 1, and a working electrode made of a mixture of Li3YBr2Cl4 and carbon powder. Sample 10 is similar to Sample 9, and the only difference is that the separator is made of Li3YBr6. The cyclic voltammogram V-A diagrams of Samples 9 and 10 during the first charge / oxidation cycle are included in Figure 5 and the cyclic voltammogram V-A diagrams during the second charge / oxidation cycle are included in Figure 6 The scan rate is 0.5 mV / s, and the cell area is 0.5 cm 2 .

[0366] Compared to Sample 10, Sample 9 exhibited significantly slower oxidative decomposition when the bias voltage exceeded the electrochemical stability critical value during the first and second charging processes of the battery pack. Specifically, in the first charging cycle, while the oxidation peak observed for Sample 10 had a current of more than 280 μA, Sample 9 exhibited an oxidation current of less than 40 μA. Figure 6 In the second charge cycle / oxidation shown, sample 9 shows no decomposition at medium bias, while sample 10 still shows decomposition.

[0367] Example 3

[0368] The halide material samples represented are formed using a process with accelerated cooling as described in the embodiments of the present invention. In short, ammonium-containing LYB and ammonium-containing LYC are formed in separate solutions, which are then combined and dried at 120°C. By heating the reaction mixture to 550°C, solid-state reaction and sublimation of ammonium are carried out in parallel. The cooling rate is about 100°C. Single-phase LYBC samples, LYBC-19, LYBC-41, LYBC-62, LYBC-67, LYBC-79 and LYBC-91 are formed. Single-phase LYB and LYC are formed in the presence of ammonium. The ionic conductivity of the samples is measured as described in the embodiments of the present invention. As described in Table 2, samples LYBC-62, LYBC-67 and LYBC-79 show unexpectedly high ionic conductivity compared to LYB.

[0369] Table 2

[0370]

[0371] Fig. 9A Included are the powder XRD pattern of sample LYBC-79 and the reference XRD pattern of LYC. Both materials are isostructural with LYBC-79, showing a lattice parameter expansion compared to LYC, as indicated by the peaks shifted to the left.

[0372] Fig. 9B Included are the powder XRD pattern of sample LYBC-67 and the reference XRD pattern of LYB. Both materials are isostructural with LYBC-67 showing a contraction of the lattice parameters compared to LYB, as indicated by the peaks shifted to the right.

[0373] Example 4

[0374] Representative halide materials were formed in the same manner as described in Example 10. Bands at crystallographic phase transition boundaries (MPBs) and phase transition ranges that may allow halide material samples to have improved ionic conductivity are included in Tables 3-5.

[0375] Table 3

[0376]

[0377] Table 4

[0378] composition <![CDATA[MPB b / (b+b’) t ]]> Range b / (b+b') <![CDATA[Li3(Y 0.85 In 0.15 )Cl6]]> 0.80 0.67-0.93

[0379] Table 5

[0380] composition <![CDATA[MPB a / (a+a’) t ]]> Range a / (a+a') <h2 style=";text-align:left;direction:ltr"><![CDATA[Li <h2 style=";text-align:left;direction:ltr"> 0.955 <h2 style=";text-align:left;direction:ltr"> (Y<h2 style=";text-align:left;direction:ltr"> 0.045 <h2 style=";text-align:left;direction:ltr"> )3Y1Cl6]]><h2 style=";text-align:left;direction:ltr"> 0.95 0.942-0.958

[0381] Example 12

[0382] The following samples were formed and the electrochemical stability of the electrolytes of the samples was tested. Cell 60 included an In / Li foil anode, a Li3Y(Cl 0.8 Br 0.2 )6 single-phase solid solution electrolyte, and Li3Y(Cl 0.8 Br 0.2 )6 and carbon powder. Battery 74 is similar to battery 60, except that Li3Y(Cl 0.8 Br 0.2 )6 was formed in the same manner as described in Example 10 into a single-phase Li3Y(Cl 0.65 Br 0.35 )6 is replaced. Battery 69 is similar to battery 60, except that Li3Y(Cl 0.8 Br 0.2 )6 was replaced by Li3YBr6 to form sample battery 69.

[0383] Fig.11A and Fig. 11B Included is a graphical representation of the results of electrolyte electrochemical stability testing by cyclic voltammetry (CV) method. Fig.11A The scans of the first charge and discharge cycle of the battery sample are included. The voltage is relative to the Li-In anode of the sample tested. As shown, when the voltage exceeds 2.9V, the electrolyte (Li3YBr6) of battery 69 begins to decompose, characterized by a relatively high current in the measurement, which indicates that the Li3YBr6 electrolyte has limited electrochemical stability at the test voltage. Compared with battery 69, the Li3Y(Cl 0.8 Br 0.2 )6 and Li3Y(Cl 0.65 Br 0.35 )6 exhibits a significantly lower current at the same voltage, which indicates that Li3Y(Cl 0.8 Br 0.2 )6 and Li3Y(Cl 0.65 Br 0.35 )6 has significantly improved electrochemical stability. Compared with Li3YBr6, Li3Y(Cl 0.65 Br 0.35 )6 seems to start at a similar voltage, but Li3Y(Cl 0.65 Br 0.35 )6 has a significantly lower decomposition kinetic (as characterized by current) than Li3YBr6. 0.65 Br 0.35 )6 and Li3YBr6, Li3Y(Cl 0.8 Br 0.2 )6 starts to decompose at a higher voltage, and the decomposition kinetics are also significantly lower than that of Li3Y(Cl 0.65 Br 0.35 )6 and Li3YBr6. Without wishing to be bound by any theory, Li3Y(Cl 0.8 Br 0.2 )6 and Li3Y(Cl 0.65 Br 0.35 The improved stability of )6 can be attributed to the effect of forming a thin Cl-rich passivation layer on the cathode.

[0384] like Fig. 11B As shown, when the voltage exceeds 3.2 V, Li3Y(Cl 0.8 Br 0.2 )6 began to decompose, showing a higher 0.65 Br 0.35 )6 Better electrochemical stability. Li3Y(Cl 0.8 Br 0.2 The improved electrochemical stability of )6 is unexpected, especially considering the comparison with Li3Y(Cl 0.65 Br 0.35 )6, Li3Y(Cl 0.8 Br 0.2 )6 has a higher Cl / Br ratio and a non-layered crystalline structure.

[0385] The operating voltage of the prior art cathode (NMC cathode) relative to the 3.7V of the Li-In anode is Fig. 11B , which corresponds to 4.3 V vs. Li / Li+ anode. It can be observed that Li3Y(Cl 0.8 Br 0.2 )6 has excellent electrochemical stability as indicated by improved decomposition kinetics characterized by lower current at the operating voltage of the NMC cathode.

[0386] Example 13

[0387] Sample CS13 was synthesized as follows. The target formula was Li3YCl3Br3. 28.23 g of Y2O3, 176.52 g of NH4Cl, and 65.13 g of LiBr were weighed so that the molar ratio between Y2O3, NH4Cl, and LiBr was Y2O3:NH4Cl:LiBr=1:13.2:6 (i.e., weighed so that the amount of NH4Cl was excessive relative to the amount of Y2O3 so as to be 10 mol% greater than the predetermined amount based on the stoichiometric ratio). The raw materials were weighed and crushed, and the fine powders were mixed in a quartz crucible under a nitrogen atmosphere with a dew point of less than or equal to -80°C. The synthesis was carried out in a furnace that had been ventilated with N2 for 24 hours. The crucible was heated to 200°C at a heating rate of 50°C per hour and maintained for 15 hours, and then the temperature was raised to 496°C at 50°C per hour and maintained in a nitrogen atmosphere for 1 hour. The crucible was cooled to room temperature, about 25°C, and then heated at a heating rate of about 100°C per hour. The temperature was monitored by using a thermocouple positioned inside the crucible. The crucible with the synthetic material was protected and positioned in a glove box under moisture-free conditions (dew point -80°C) to unload the synthetic block from the crucible. Organic residues on the upper surface of the synthetic block were removed. The obtained block was crushed into powder in a glove box under N2 atmosphere.

[0388] The ground powder of sample CS13 was subjected to XRD analysis under dry conditions. The powder showed a hexagonal crystalline structure similar to conventionally prepared Li3YCl6. Lebail refinement was performed using the XRD spectrum to determine the Br / Cl ratio in the material by lattice parameter expansion. The ratio of Cl or Br to the total amount of anions (i.e., the total amount of Cl and Br) was calculated, where the ratio of Br to the total amount of Cl and Br was 28% ± 2%, and the ratio of Cl to the total amount of Cl and Br was 72% ± 2%.

[0389] Lebail's refinement was performed by processing the XRD pattern with the FullProf software package. The background of the diffraction pattern was first extracted by an automated procedure of the winPLOTR software. The XRD pattern was then refined using the Lebail method implemented in the FullProf software by using the P-3m1 space group and by refining the lattice parameters (i.e., a, b, and c), the sample height correction parameter ("zero point"), and the Lorentzian components associated with the size and strain of the particles in the sample. The refinement was considered fully converted when the chi2 parameter was found to be below 6.

[0390] The total content of the water-insoluble impurity phase of sample CS13 was determined as described in the embodiments herein. In brief, 50 g of ground sample CS13 was dissolved in distilled water. Even though the solution looked pure, 60 mg of hydrated insoluble impurities (e.g., YCl(OH)2) were collected from the filter. Relative to the total weight of the water-insoluble impurities, the total content of the water-insoluble impurities of sample CS13 was 53.2 mg, consisting of YOCl. Sample CS13 included a total content of 0.11 wt % of the water-insoluble impurity phase.

[0391] Representative sample S14 was formed as follows: The target formula was Li3YCl3Br3.

[0392] 27.71 g of Li2CO3, 28.23 g of Y2O3, 192 ml of 47% concentrated HBr, 160 g of NH4Br and 50 g of distilled H2O were measured and mixed at 95° C. to form a solution of Li2YBr6 precursor material. The solution was then filtered through a 0.2 micron microporous filter.

[0393] 138.5 g of Li2CO3, 141.1 g of Y2O3, 687 ml of 37% HCl, 435 g of NH4Cl and 150 g of distilled H2O were measured separately and mixed at 95° C. to form a solution of Li3YCl6 precursor material. The solution was then filtered through a 0.2 micron micropore filter.

[0394] The two precursor materials are dried in a rotary evaporator to obtain a material in solid form. The material is crushed to form a finer powder, weighed and mixed in a quartz crucible under a nitrogen atmosphere with a dew point less than or equal to 80°C. The synthesis is carried out in a furnace that has been ventilated with N2 for 24 hours before. The crucible is heated to 540°C at a continuous heating rate of 100°C per hour and kept at 540°C for 1 hour. The crucible is cooled to room temperature, about 25°C, and then heated at a heating rate of up to 100°C per hour. The temperature is monitored by using a thermocouple positioned inside the crucible. The crucible with the synthetic material is protected and positioned in a glove box in a moisture-free condition (dew point -80°C) to unload the synthetic block from the crucible. Remove organic residues on the upper surface of the synthetic block. The obtained block is crushed into powder in a glove box under a N2 atmosphere.

[0395] XRD analysis was performed on the ground powder of sample S14 under dry conditions. The powder showed a hexagonal crystalline structure similar to conventionally prepared Li3YCl6. Lebail refinement was performed using the XRD spectrum to determine the Br / Cl ratio in the material through lattice parameter expansion.

[0396] The ratio of Cl or Br to the total amount of anions (the total amount of Cl and Br) was calculated, wherein the ratio of Br to the total amount of Cl and Br was 20%±2%, and the ratio of Cl to the total amount of Cl and Br was 80%±2%.

[0397] The total content of the water-insoluble impurity phase of sample S14 was determined as described in the embodiments herein. Briefly, 50 g of ground sample S14 was dissolved in distilled water. 9 mg of hydrated insoluble impurities were collected from the filter, corresponding to 8.1 g of non-hydrated water-insoluble impurities. Sample S14 had a total content of 0.016 wt % of water-insoluble impurities relative to the total weight of the halide material.

[0398] Two symmetrical battery cells were formed including stainless steel electrodes and a pressed electrolyte made with the powder of sample CS 13. The ionic conductivity and thickness of the electrolyte as well as the ohmic resistance and mass of the cells were measured and included in Table 6.

[0399] Table 6

[0400]

[0401] Additional symmetrical battery cells were formed including stainless steel electrodes and a pressed electrolyte (0.98 mm thickness) made with the powder of sample S14. The ionic conductivity of the electrolyte was measured and included in Table 7.

[0402] Table 7

[0403]

[0404] The above has described the benefits, other advantages and solutions to the problems with respect to specific embodiments. However, the benefits, advantages, solutions to the problems, and any features that may cause any benefits, advantages or solutions to appear or become more significant should not be interpreted as key, essential or necessary features of any or all claims. The materials comprising one or more components mentioned herein may be interpreted as including at least one embodiment, wherein the material is substantially composed of one or more components determined. The term "substantially composed of..." will be interpreted as including a composition that includes those determined materials and excludes all other materials except a few contents (e.g., impurity contents), which do not significantly change the properties of the material. In addition, or in the alternative, in certain non-limiting embodiments, any one of the compositions determined herein may be substantially free of materials that are not clearly disclosed. The embodiments herein include content ranges of certain components in the material, and it should be understood that the content of the components in a given material totals 100%.

[0405] The description and illustration of the embodiments described herein are intended to provide a general understanding of the structure of various embodiments. Description and illustration are not intended to be used as a detailed and comprehensive description of all elements and features of the device and system using the structure or method described herein. Individual embodiments may also be provided in combination in a single embodiment, and on the contrary, the various features described in the context of a single embodiment for the sake of brevity may also be provided individually or in any sub-combination. In addition, reference to the values ​​described in the range includes each value within the range. Only after reading this specification, many other embodiments may be apparent to the technician. Other embodiments may be used and derived from the present disclosure, so that structural substitution, logical substitution or another change may be performed without departing from the scope of the present disclosure. Therefore, the present disclosure should be considered illustrative and not restrictive.< / hklm> < / hkl> < / hklm> < / hkl>

Claims

1. A solid electrolyte material comprising a halide material comprising at least two halide anions selected from the group consisting of F, Cl, Br and I and consisting of Li 3-x-f M f RE 1-y Me k y (Cl 1-u-p- q Br u F p I q ) 6-x+y*(k-3) express, in: -1<=x<=1; 0<=y<1; 0<=u<1; 0<=p<=1 / 3; 0<=q<=1 / 6; 0<(u+p+q)<1; 0<=f<=0.3; M is at least one alkali metal element other than Li; RE is a rare earth element; k is the valence of Me; and Me includes Y, Ce, Gd, Er, Sm, Eu, Pr, Tb, In, Al, Zr, La, Yb, Mg, Zn, Sn, Mg, Ca or any combination thereof, where Me is different from RE; and Wherein the total weight of the halide material relative to the halide material comprises: one or more water-insoluble impurity phases, the total content of the one or more water-insoluble impurity phases being no greater than 0.05% by weight, wherein the one or more water-insoluble impurity phases include a rare earth oxyhalide phase; and A total content of at least 0.0001 wt % and no greater than 10 wt % of a binary halide phase, wherein the binary halide phase comprises lithium halide, rare earth halide, or a combination thereof.

2. The solid electrolyte material according to claim 1, wherein the halide material includes not more than 0.03 wt% of the water-insoluble impurity phase and not more than 2 wt% of the binary halide phase relative to the total weight of the halide material.

3. The solid electrolyte material according to claim 1, wherein the at least two halide anions include Br.

4. The solid electrolyte material according to claim 1, wherein the halide material is Li 3- x RE 1-y Me k y (Cl 1-u Br u ) 6-x+y*(k-3) Indicates that 0.08<=u<=0.

67.

5. A solid electrolyte material, comprising a halide material, wherein the halide material comprises halide anions in a single phase, wherein the halide material is composed of Li 3-x RE 1-y Me k y (Cl 1-u Br u ) 6-x+y*(k-3) represents, where: -1<=x<=1; 0<=y<1; 0<u<1; RE is a rare earth element; and Me includes Y, Ce, Gd, Er, Sm, Eu, Pr, Tb, In, Al, Zr, La, Yb, Mg, Zn, Sn, Mg, Ca or any combination thereof, Where Me is different from RE, The halide material comprises: one or more water-insoluble impurity phases, the total amount of the one or more water-insoluble impurity phases being less than 0.05% by weight, wherein the one or more water-insoluble impurity phases include a rare earth oxyhalide phase; and No greater than 2 wt % of a binary halide phase relative to the total weight of the halide material, wherein the binary halide phase comprises a lithium halide, a rare earth halide, or a combination thereof. 6 . The solid electrolyte material according to claim 5 , wherein the halide material includes not more than 0.03 wt % of the water-insoluble impurity phase relative to the total weight of the halide material. 7 . The solid electrolyte material according to claim 5 , wherein the halide material comprises a crystalline structure represented by a rhombohedral space group.

8. The solid electrolyte material according to claim 7, wherein the crystalline structure includes the unit cell which is smaller than the unit cell of Li3YBr6.

9. The solid electrolyte material according to claim 5, wherein the peak of the powder diffraction pattern of the halide material is shifted to a higher angle compared to the corresponding peak of the powder diffraction pattern of Li3YBr6.

10. The solid electrolyte material according to claim 1, wherein the halide material is Li 3- x-f M f RE 1-y Me k y (Cl 1-p F p ) 6-x+y*(k-3) Indicates that 0<=p<2.

11. The solid electrolyte material according to claim 5, wherein RE comprises Y, Ce, Gd, Er, La or Yb. 12 . The solid electrolyte material according to claim 11 , wherein RE consists of Y, y>0, and Me is at least one selected from the group consisting of Gd, Yb, Zr, In, Mg, Al, and Ca.

13. The solid electrolyte material of claim 4, wherein the halide material comprises an average diffraction crystallite size of at least 25 nm.

14. An electrochemical device, comprising: A solid electrolyte layer comprising the solid electrolyte material according to claim 1, wherein the halide material comprises Cl and F; An electrode layer comprising a cathode active material in contact with the solid electrolyte material, wherein the solid electrolyte layer is capable of forming a chlorine-deficient or fluorine-deficient region proximate to the electrode layer under oxidizing conditions, wherein the chlorine-deficient or fluorine-deficient region contains a lower concentration of chlorine or fluorine, respectively, than a region of the solid electrolyte layer away from the electrode layer.

15. A solid electrolyte material, comprising Li a M a' Me b Me' b’ X c X' c’ Represents the halide material, wherein the halide material has a crystallographic phase transition within the following stoichiometric range: (b / (b+b')) t *0.84 t *1.16, where (b / (b+b')) t Corresponding to the crystallographic phase transition on the crystallographic phase diagram at a temperature of 20°C to 25°C;​ (c / (c+c')) t *0.84 <c / (c+c’)<(c / (c+c’)) t *1.16, where (c / (c+c')) t Corresponding to the crystallographic phase transition on the crystallographic phase diagram at a temperature of 20°C to 25°C; or (a / (a+a')) t *0.84 t *1.16, among which (a / (a+a')) t Corresponding to the crystallographic phase transition on the crystallographic phase diagram at a temperature of 20°C to 25°C;​ in: Me is at least one rare earth element; Me′ is different from Me and includes Y, Ce, Gd, Er, Sm, Eu, Pr, Tb, In, Al, Zr, La, Yb, Mg, Zn, Sn, Mg, Ca, or any combination thereof; wherein b>=b'; c>=c'; a>=a'; X is at least one halogen other than X'; X' is a halogen; and M is at least one alkali metal element other than Li; and wherein the anion of the halide material comprises at least one of Cl or Br and is in a single phase; and The halide material comprises: one or more water-insoluble impurity phases, the total amount of the one or more water-insoluble impurity phases being less than 0.05% by weight, wherein the one or more water-insoluble impurity phases include a rare earth oxyhalide phase; and No greater than 5 wt % of a binary halide phase relative to the total weight of the halide material, wherein the binary halide phase comprises a lithium halide, a rare earth halide, or a combination thereof.

16. The solid electrolyte material according to claim 15, wherein the crystallographic phase transition comprises: transition from a layered to a non-layered crystal structure; The transition from a cubic close-packed structure to a hexagonal close-packed structure; Transition from C2 / m space group or R-3m space group to P-3m1 or Pnma space group; Transition from a non-layered crystal structure to another non-layered crystal structure or to a layered crystal structure; The transition from R3c to R3m; or a transition from P-3m1 or Pnma space group to C2 / m space group or R-3m space group, and Wherein, relative to the total weight of the halide material, the total content of the binary halide phase is not greater than 2 weight %.

17. The solid electrolyte material according to claim 15, wherein the halide material is Li a-f M a’ RE b Me' k b’ (Cl c Br C’ ) 6-f+(k-3)*b’ represents, where: a+a'=3; -1≤f≤1; c+c'=1; and b+b'=1, and Wherein, relative to the total weight of the halide material, the total content of the binary halide phase is not greater than 2 weight %.

18. The solid electrolyte material according to claim 15, wherein the halide material is Li 3-f RE b Me' k b’ (Cl c Br c’ ) 6-f+(k-3)*b’ represents, where: -1≤f≤1; (c+c')=1; b>0; b’>0; 0.65≤c / (c+c')≤0.95; and (b+b')=1; and Wherein, relative to the total weight of the halide material, the total content of the binary halide phase is not greater than 2 weight %.

19. The solid electrolyte material according to claim 15, wherein the halide material is Li 3-f RE(Cl c Br c’ ) 6-f represents, where: RE includes Y; 0<=f<=0.3; c+c'=1; and 0.63≤c / (c+c')≤0.87; and Wherein, relative to the total weight of the halide material, the total content of the binary halide phase is not greater than 2 weight %.

20. The solid electrolyte material according to claim 15, wherein the halide material is Li a M a’ REX6 said that among them: a>a'>0; a+a'=3; and 0.942≤a / (a+a')≤0.958; and Wherein, relative to the total weight of the halide material, the total content of the binary halide phase is not greater than 2 weight %.

Citation Information

Patent Citations

  • Method for producing halides

    CN112739653A